Injection-molded article and method for producing the same

The introduction of crosslinked resin particles with a high gel fraction into a thermoplastic resin composition addresses the limitations of impact resistance and mold release in existing injection molded products, resulting in a product with enhanced mechanical strength and environmental compatibility.

JP2025063464APending Publication Date: 2025-04-16KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023172683
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing injection molded products made from thermoplastic resin compositions, such as those described in Patent Document 1, lack sufficient impact resistance and exhibit poor mold release and bleed-out resistance.

Method used

A thermoplastic resin composition is developed, comprising 40 to 99 parts by weight of a thermoplastic resin (A) and 1 to 60 parts by weight of crosslinked resin particles (B), where the crosslinked resin particles contain a polyhydroxyalkanoate resin with a gel fraction of 50% or more, enhancing the impact resistance, mold release, and bleed-out resistance of the injection molded body.

Benefits of technology

The resulting injection molded body achieves excellent impact resistance, along with improved mold release and bleed-out resistance, ensuring higher mechanical strength and productivity while maintaining environmental sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063464000001
    Figure 2025063464000001
  • Figure 2025063464000002
    Figure 2025063464000002
Patent Text Reader

Abstract

To provide an injection-molded article having superior impact resistance, mold releasability, and bleed-out resistance.SOLUTION: An injection-molded article is prepared by molding a thermoplastic resin composition that comprises 40 to 99 pts.wt. of thermoplastic resin (A) and 1 to 60 pts.wt. of crosslinked resin particles (B) containing a polyhydroxyalkanoate-based resin and having a gel fraction of 50% or more, wherein the composition has an Elmendorf tear strength of 5 N / mm or more when molded into a film with a thickness of 110 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an injection molded article and a method for producing the same. [Background technology]

[0002] Plastic waste places a burden on the global environment, affecting ecosystems, emitting harmful gases when burned, and contributing to global warming through the large amount of heat generated by combustion. There has been active development of biodegradable plastics as a material that can solve these problems.

[0003] Patent Document 1 describes a biodegradable and environmentally compatible thermoplastic resin composition that is obtained by blending 0.1 to 20 parts by weight of poly(3-hydroxyalkanoate) particles having an average particle size of 300 μm or less with 100 parts by weight of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate). Patent Document 1 also describes that the thermoplastic resin composition can be processed into a molded product by injection molding or the like. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2004-161802 A Summary of the Invention [Problem to be solved by the invention]

[0005] The technique of blending poly(3-hydroxyalkanoate) particles with a thermoplastic resin as described in Patent Document 1 can improve the flexibility of the thermoplastic resin, but does not contribute to improving the impact resistance of the thermoplastic resin. Therefore, the injection-molded product obtained by molding the thermoplastic resin composition described in Patent Document 1 has room for improvement in terms of impact resistance.

[0006] Patent Document 1 also discloses that the crystallization promotion effect can be obtained by further adding a plasticizer to the thermoplastic resin composition. It is known that when crystallization is promoted, the mechanical strength of the thermoplastic resin composition is improved, and the physical properties such as impact resistance of molded articles such as injection molded articles are also improved. However, the present inventors have found that the injection molded article made of the thermoplastic resin composition to which a plasticizer is further added has problems such as poor mold releasability and the occurrence of bleed-out.

[0007] In view of the above-mentioned current situation, an object of the present invention is to provide an injection molded article which has excellent impact resistance, as well as excellent mold releasability and bleed-out resistance. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that mechanical strength such as impact strength is improved in a thermoplastic resin composition obtained by blending crosslinked resin particles composed of a polyhydroxyalkanoate resin and having a specific gel fraction with a thermoplastic resin. The present inventors have also found that an injection molded article obtained by molding a thermoplastic resin composition obtained by blending the crosslinked resin particles with a thermoplastic resin has excellent impact resistance, as well as excellent mold releasability and bleed-out resistance. Based on the above, the present inventors have completed the present invention.

[0009] That is, an injection molded article according to one embodiment of the present invention is an injection molded article obtained by molding a thermoplastic resin composition, The thermoplastic resin composition comprises 40 parts by weight to 99 parts by weight of a thermoplastic resin (A) and 1 part by weight to 60 parts by weight of crosslinked resin particles (B) (wherein the total amount of (A) and (B) is 100 parts by weight), The crosslinked resin particles (B) contain a polyhydroxyalkanoate resin and have a gel fraction of 50% or more, The thermoplastic resin composition relates to an injection-molded article having an Elmendorf tear strength of 5 N / mm or more as measured by the following methods (1) to (4); (1) The thermoplastic resin composition is molded into a sheet having a thickness of 110 μm to obtain a press sheet. (2) The press sheet obtained in step (1) is aged under conditions of 23° C. and 50% RH for 7 days to obtain a film sample. (3) The film sample obtained in step (2) is subjected to measurement of tear strength (unit: N) according to the Elmendorf tear method specified in JIS K7128-2. (4) The tear strength measured in (3) is divided by the thickness (unit: mm) of the film sample to calculate the Elmendorf tear strength.

[0010] Further, a method for producing an injection molded article according to one embodiment of the present invention is a method for producing an injection molded article according to one embodiment of the present invention, an injection step of injecting the thermoplastic resin composition into a mold; a cooling step of cooling and solidifying the thermoplastic resin composition in the mold injected in the injection step to form an injection molded article; and The present invention relates to a method for producing an injection molded article, the method including a removal step of removing the injection molded article obtained in the cooling step from inside the mold. Effect of the Invention

[0011] The injection molded article according to one embodiment of the present invention has the effect of being excellent in mold releasability and bleed-out resistance in addition to excellent impact resistance. Also, the manufacturing method for an injection molded article according to one embodiment of the present invention has the effect of being able to manufacture an injection molded article having excellent mold releasability and bleed-out resistance in addition to excellent impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more, B or less". In addition, all documents described in this specification are incorporated by reference in this specification.

[0013] [1. Injection molded product] An injection molded article according to one embodiment of the present invention (hereinafter also referred to as "the present injection molded article") is an injection molded article obtained by molding a thermoplastic resin composition, The thermoplastic resin composition comprises 40 parts by weight to 99 parts by weight of a thermoplastic resin (A) and 1 part by weight to 60 parts by weight of crosslinked resin particles (B) (wherein the total amount of (A) and (B) is 100 parts by weight), The crosslinked resin particles (B) contain a polyhydroxyalkanoate resin and have a gel fraction of 50% or more, The thermoplastic resin composition has an Elmendorf tear strength of 5 N / mm or more, as measured by the following methods (1) to (4); (1) The thermoplastic resin composition is molded into a sheet having a thickness of 110 μm to obtain a press sheet. (2) The press sheet obtained in step (1) is aged under conditions of 23° C. and 50% RH for 7 days to obtain a film sample. (3) The film sample obtained in step (2) is subjected to measurement of tear strength (unit: N) according to the Elmendorf tear method specified in JIS K7128-2. (4) The tear strength measured in (3) is divided by the thickness (unit: mm) of the film sample to calculate the Elmendorf tear strength.

[0014] The thermoplastic resin composition constituting the present injection molded article contains a thermoplastic resin (A), while containing crosslinked resin particles (B) containing a polyhydroxyalkanoate resin and having a gel fraction of 50% or more, thereby improving the impact resistance of the thermoplastic resin (A). Therefore, the thermoplastic resin composition has excellent impact resistance, and as a result, the present injection molded article molded from the thermoplastic resin composition also has excellent impact resistance. In addition, in the following, the expression "Elmendorf tear strength" means the Elmendorf tear strength measured by the method shown in (1) to (4) above. The Elmendorf tear strength is the tear strength of a film obtained by molding the thermoplastic resin composition into a predetermined film shape. Here, the Elmendorf tear strength of 5 N / mm or more indicates that the mechanical strength of the thermoplastic resin composition itself constituting the film is excellent. Therefore, the present injection molded article is molded from a thermoplastic resin composition having excellent mechanical strength due to the Elmendorf tear strength of 5 N / mm or more, and as a result, has excellent impact resistance.

[0015] In addition, the thermoplastic resin composition of the injection molded article has excellent impact resistance without containing a plasticizer that reduces mold releasability and bleed-out resistance. Therefore, the injection molded article has excellent impact resistance, as well as excellent mold releasability and bleed-out resistance.

[0016] Each component of the injection molded article will be described in detail below.

[0017] [1-1. Thermoplastic resin composition] The thermoplastic resin composition constituting the present injection molded article will be described below. First, the crosslinked resin particles (B) will be described.

[0018] <Crosslinked resin particles (B)> The crosslinked resin particles (B) are particles composed of a polyhydroxyalkanoate resin as a main resin component. Hereinafter, the polyhydroxyalkanoate resin may be abbreviated as "PHA."

[0019] (PHAs) "PHA" is a general term for polymers containing hydroxyalkanoic acid as a monomer unit (monomer repeating unit), and is generally biodegradable. PHA is an aliphatic polyester, preferably a polyester not containing an aromatic ring. In this specification, "PHA" refers to a polymer containing hydroxyalkanoic acid repeating units in an amount of 50 mol% or more of all monomer repeating units (100 mol%). PHA preferably contains hydroxyalkanoic acid repeating units in an amount of 60 mol% or more, more preferably 70 mol% or more, of all monomer repeating units (100 mol%).

[0020] There is no particular limitation on the PHA. Examples of PHA include polyglycolic acid, poly(3-hydroxyalkanoate)-based resin (hereinafter sometimes referred to as "P3HA"), poly(4-hydroxyalkanoate)-based resin, and the like. As the PHA, only one type may be used alone, or two or more types may be used in combination. The PHA preferably contains a poly(3-hydroxyalkanoate)-based resin, and more preferably is a poly(3-hydroxyalkanoate)-based resin (in other words, composed only of a poly(3-hydroxyalkanoate)-based resin).

[0021] In this specification, "polyglycolic acid" refers to a compound having a repeating monomer unit of [-CH 2 The term "polyglycolic acid" refers to a resin containing 50 mol % or more of repeating units represented by the formula [-CH 2 The repeating units represented by the formula: --CO-O-- may account for 60 mol % or more, 70 mol % or more, 80 mol % or more, or 90 mol % or more of all monomer repeating units (100 mol %).

[0022] The polyglycolic acid may be a homopolymer of glycolic acid, or a copolymer of glycolic acid and a monomer other than glycolic acid (for example, a copolymer of glycolic acid and lactic acid, a copolymer of glycolic acid and caprolactone, etc.).

[0023] Polyglycolic acid can be obtained by known methods such as condensation polymerization of glycolic acid and ring-opening polymerization of glycolide.

[0024] The P3HA has the formula: [-CHR-CH 2 -CO-O-] (wherein R is C n H 2n+1 where n is an integer of 1 or more and 15 or less.) is a polyhydroxyalkanoate containing the 3-hydroxyalkanoic acid repeating unit as an essential repeating unit. In this specification, "P3HA" refers to a resin containing 50 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %). The P3HA preferably contains 60 mol % or more, and more preferably 70 mol % or more of the 3-hydroxyalkanoic acid repeating unit out of all monomer repeating units (100 mol %).

[0025] P3HA is not particularly limited, and may be a homopolymer containing the repeating unit described above, or a copolymer containing the repeating unit described above. Examples of the copolymer include copolymers of 3-hydroxybutanoic acid (hereinafter sometimes referred to as "3HB") and one or more monomers selected from the group consisting of 3-hydroxypropionic acid, 3-hydroxypentanoic acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid, 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, 3-hydroxyundecanoic acid, 3-hydroxydodecanoic acid, 3-hydroxytridecanoic acid, 3-hydroxytetradecanoic acid, 3-hydroxyhexadecanoic acid, and 3-hydroxyoctadecanoic acid. Alternatively, another example of the copolymer may be, for example, a copolymer of 3HB and one or more monomers selected from the group consisting of 4-hydroxybutanoic acid, 4-hydroxypentanoic acid, 4-hydroxyhexanoic acid, 4-hydroxyheptanoic acid, 4-hydroxyoctanoic acid, 4-hydroxynonanoic acid, 4-hydroxydecanoic acid, 4-hydroxyundecanoic acid, 4-hydroxydodecanoic acid, 4-hydroxytridecanoic acid, 4-hydroxytetradecanoic acid, 4-hydroxyhexadecanoic acid, and 4-hydroxyoctadecanoic acid.

[0026] Examples of P3HA include poly(3-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB"), which is a homopolymer of 3HB, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter, sometimes referred to as "P3HB3HH"), and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (hereinafter, sometimes referred to as "P3HB4HB"). Only one type of P3HA may be used, or two or more types may be used in combination. In this specification, "poly(X-co-Y)" refers to a copolymer containing X repeating units and Y repeating units, and is intended to mean a copolymer obtained by copolymerizing a monomer from which the X repeating units are derived and a monomer from which the Y repeating units are derived. In addition, during the production of P3HA by a microorganism, a small amount (about 1 mol% or less) of a monomer may be copolymerized, but if it does not significantly affect the physical properties of the obtained P3HA, the monomer is considered to be not copolymerized, and the product is called by a name that does not include the monomer.

[0027] P3HA can be produced by microorganisms. Such microbially produced P3HA is usually P3HA composed only of D-form (R-form) 3-hydroxyalkanoic acid repeating units. Among the microbially produced P3HA, P3HB, P3HB3HH and P3HB4HB are preferred, and P3HB3HH and P3HB4HB are more preferred, because they are easy to produce industrially.

[0028] It is also preferred that P3HA contains a 3-hydroxybutanoic acid (3HB) repeating unit. When P3HA contains a 3HB repeating unit, the composition ratio of the 3HB repeating unit in the total monomer repeating units (100 mol%) is preferably 60 mol% to 99 mol%, more preferably 61 mol% to 97 mol%, and even more preferably 62 mol% to 95 mol%, from the viewpoint of the balance between flexibility and strength. When the composition ratio of the 3HB repeating unit in P3HA is 60 mol% or more, there is an advantage that the rigidity of the crosslinked resin particle (B) can be further improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, there is an advantage that the flexibility of the crosslinked resin particle (B) tends to be further improved. The monomer composition ratio of P3HA can be measured by gas chromatography or the like (for example, see International Publication No. 2014 / 020838). As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.

[0029] Microorganisms that produce P3HA are not particularly limited as long as they have the ability to produce P3HA. For example, the first P3HB-producing bacterium was Bacillus megaterium, discovered in 1925, and other natural microorganisms such as Cupriavidus necator (formerly classified as Alcaligenes eutrophus and Ralstonia eutropha) and Alcaligenes latus are also known. In these microorganisms, P3HB accumulates within the bacterial cells.

[0030] Also, as producers of copolymers of 3HB and other hydroxyalkanoic acids, Aeromonas caviae, which produces P3HB3HH, and Alcaligenes eutrophus, which produces poly(3-hydroxybutyrate-co-4-hydroxybutyrate), are known. In particular, in order to increase the productivity of P3HB3HH, Alcaligenes eutrophus AC32 (FERM BP-6038) (T. Fukui, Y. Doi, J. Bateriol., 179, p4821-4830 (1997)) into which genes of P3HA synthase group have been introduced is preferred. Microorganisms that have been cultured under appropriate conditions to accumulate P3HA in the cells are used. In addition to the above, genetically modified microorganisms into which various P3HA synthesis-related genes have been introduced may be used depending on the P3HA to be produced, and culture conditions, including the type of substrate, may be optimized.

[0031] The weight average molecular weight of the PHA is not particularly limited. The weight average molecular weight of the PHA is preferably 50,000 to 3,000,000, preferably 100,000 to 2,000,000, and more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the crosslinked resin particles (B) to have a low strength can be reduced or avoided. Also, when the weight average molecular weight of the PHA is 50,000 or more, it has an advantage that the tendency of the low molecular weight component to be sticky can be reduced or avoided. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less can have an advantage that the PHA is easy to manufacture and / or that the PHA is easy to handle in order to achieve the object of one embodiment of the present invention. The numerical value of the weight average molecular weight of the PHA is a value obtained by measuring the PHA before the crosslinking treatment.

[0032] The weight average molecular weight can be measured by using gel permeation chromatography (GPC) (Shimadzu Corporation's "High Performance Liquid Chromatograph 20A System"), polystyrene gel (Showa Denko KK's "KG 4A", "K-806M", etc.) as a column, and chloroform as a mobile phase. The weight average molecular weight can be determined as a molecular weight converted into polystyrene using a calibration curve obtained by measuring polystyrene with a known molecular weight by the same measurement method. In this case, the calibration curve can be created using polystyrene with weight average molecular weights of 31,400, 197,000, 668,000, and 1,920,000. As the column for the GPC, a column appropriate for measuring the molecular weight may be used.

[0033] (Gel fraction) In this specification, the term "crosslinked resin particles (B)" refers to a resin particle having a crosslinked structure in which molecular chains of the resin constituting the resin particles are bonded intramolecularly and / or intermolecularly. That is, the crosslinked resin particles (B) may have a crosslinked structure in which molecular chains of PHA are bonded together. The amount of crosslinked structures in the crosslinked resin particles (B) affects the gel fraction of the crosslinked resin particles (B), and specifically, the more crosslinked structures there are, the higher the gel fraction becomes. The crosslinked resin particles (B) have a certain amount or more of crosslinked structures, and therefore exhibit a high gel fraction, specifically, a gel fraction of 50% or more. The crosslinked resin particles (B) have a gel fraction of 50% or more, and therefore have excellent hardness, heat resistance, and solvent resistance.

[0034] The value of the gel fraction is preferably 60% or more, more preferably 70% or more, even more preferably 75% or more, and particularly preferably 80% or more. It may also be 85% or more, or 90% or more. The upper limit of the gel fraction is not particularly limited, and may be 100% or less. From the viewpoint of production efficiency of the crosslinked resin particles (B), the upper limit of the gel fraction is preferably 99.5% or less, more preferably 99% or less. The upper limit of the gel fraction may also be 98% or less, 97% or less, or 96% or less.

[0035] The gel fraction is a value measured as follows: (1) A dried product of the crosslinked resin particles (B) is added to chloroform so that the concentration becomes 0.7% by weight, and the resulting mixture is kept at 60°C for 30 minutes to obtain a chloroform solution; (2) After that, the chloroform solution is allowed to stand at room temperature for 3 hours, and then the chloroform solution is filtered through a membrane filter having a pore size of 0.45 μm; (3) The gel remaining on the filter is dried, and the weight of the dried gel together with the filter is measured, and the gel fraction is calculated using the following formula. Formula: gel fraction (%)={(weight of filter including dried gel−weight of filter only) / weight of dried crosslinked resin particles (B) used in measurement}×100.

[0036] (Volume average particle size) The volume average particle diameter of the crosslinked resin particles (B) is preferably 0.10 μm to 10.00 μm. This configuration allows the crosslinked resin particles (B) to be suitably used in various applications as described below. From the viewpoint of practical use opportunities, the lower limit of the volume average particle diameter is more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, from the viewpoint of productivity (production of PHA and / or crosslinking treatment, etc.), the upper limit of the volume average particle diameter is more preferably 8.00 μm or less, and even more preferably 5.00 μm or less.

[0037] In this specification, the volume average particle diameter (MV) of the crosslinked resin particles (B) is a value obtained by measuring the crosslinked resin particles (B) using an aqueous dispersion liquid in which the crosslinked resin particles (B) are dispersed in an aqueous medium. More specifically, the volume average particle diameter (MV) of the crosslinked resin particles (B) is a value calculated by the following formula (1), i.e., formula (2), when the particle diameters of the individual crosslinked resin particles (B) contained in a group of k total crosslinked resin particles (B) are d1, d2,...di...dk in ascending order, and the volumes of the individual crosslinked resin particles (B) are V1, V2,...Vi...Vk (here, the volume of the crosslinked resin particles (B) with particle diameter di is Vi).

number

[0038] (Peroxide) The crosslinked structure in the crosslinked resin particles (B) is not particularly limited, but is preferably crosslinked using a peroxide. That is, the crosslinked resin particles (B) are preferably crosslinked using a peroxide. When a peroxide is used, radicals generated by decomposition of the peroxide act on the molecules of the resin (e.g., PHA) constituting the resin particles. This allows the molecular chains of the resin constituting the resin particles to be directly bonded to each other, forming a crosslinked structure.

[0039] When the crosslinked resin particles (B) are crosslinked using a peroxide, the aqueous dispersion containing the crosslinked resin particles (B) may contain substances derived from the peroxide used to introduce the crosslinked structure (such as decomposition products of the peroxide and unreacted peroxide). Alternatively, when the crosslinked resin particles (B) are crosslinked using a peroxide, substances derived from the peroxide used to introduce the crosslinked structure (such as decomposition products of the peroxide and unreacted peroxide) may adhere to the surface of the obtained crosslinked resin particles (B). That is, when the crosslinked resin particles (B) are crosslinked using a peroxide, the crosslinked resin particles (B) or the injection molded article may contain substances derived from the peroxide (such as decomposition products of the peroxide and unreacted peroxide). When the crosslinked resin particles (B) or the injection molded article contain substances derived from the peroxide, it is found that the crosslinked resin particles (B) are crosslinked using a peroxide by analyzing the crosslinked resin particles (B) or the injection molded article.

[0040] The peroxide may be an organic peroxide or an inorganic peroxide. The peroxide is preferably an organic peroxide because it can increase the gel fraction more efficiently.

[0041] As the organic peroxide, it is preferable to use at least one selected from the group consisting of diacyl peroxides, alkyl peroxy esters, dialkyl peroxides, hydroperoxides, peroxy ketals, peroxy carbonates, and peroxy dicarbonates, taking into consideration the heating temperature and / or time during the crosslinking treatment.

[0042] Specific examples of such organic peroxides include butyl peroxy neododecanoate, octanoyl peroxide, dilauroyl peroxide, succinic peroxide, a mixture of toluoyl peroxide and benzoyl peroxide, benzoyl peroxide, bis(butylperoxy)trimethylcyclohexane, butylperoxylaurate, dimethyldi(benzoylperoxy)hexane, bis(butylperoxy)methylcyclohexane, bis(butylperoxy)cyclohexane, and butylperoxybenzo. ester, butyl bis(butylperoxy)valerate, dicumyl peroxide, di-t-hexyl peroxide, t-butylperoxy 2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxymethyl monocarbonate, t-pentylperoxymethyl monocarbonate, t-hexylperoxymethyl monocarbonate, t-heptylperoxymethyl monocarbonate, t-octylperoxymethyl monocarbonate, 1 ,1,3,3-tetramethylbutylperoxymethyl monocarbonate, t-butylperoxyethyl monocarbonate, t-pentylperoxyethyl monocarbonate, t-hexylperoxyethyl monocarbonate, t-heptylperoxyethyl monocarbonate, t-octylperoxyethyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyethyl monocarbonate, t-butylperoxy n-propyl monocarbonate, t-pentylperoxy n-propyl monocarbonate, t-hexylperoxyethyl monocarbonate peroxy n-propyl monocarbonate, t-heptyl peroxy n-propyl monocarbonate, t-octyl peroxy n-propyl monocarbonate, 1,1,3,3-tetramethylbutyl peroxy n-propyl monocarbonate, t-butyl peroxy isopropyl monocarbonate, t-pentyl peroxy isopropyl monocarbonate, t-hexyl peroxy isopropyl monocarbonate, t-heptyl peroxy isopropyl monocarbonate, t-octyl peroxy isopropyl monocarbonate, 1,1,3,3-Tetramethylbutylperoxyisopropyl monocarbonate, t-butylperoxyn-butyl monocarbonate, t-pentylperoxyn-butyl monocarbonate, t-hexylperoxyn-butyl monocarbonate, t-heptylperoxyn-butyl monocarbonate, t-octylperoxyn-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxyn-butyl monocarbonate, t-butylperoxyisobutyl monocarbonate, t-pentylperoxyisobutyl monocarbonate, t -Hexylperoxyisobutylmonocarbonate, t-heptylperoxyisobutylmonocarbonate, t-octylperoxyisobutylmonocarbonate, 1,1,3,3-tetramethylbutylperoxyisobutylmonocarbonate, t-butylperoxysec-butylmonocarbonate, t-pentylperoxysec-butylmonocarbonate, t-hexylperoxysec-butylmonocarbonate, t-heptylperoxysec-butylmonocarbonate, t-octylperoxysec-butylmonocarbonate peroxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy sec-butyl monocarbonate, t-butylperoxy t-butyl monocarbonate, t-pentylperoxy t-butyl monocarbonate, t-hexylperoxy t-butyl monocarbonate, t-heptylperoxy t-butyl monocarbonate, t-octylperoxy t-butyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy t-butyl monocarbonate, t-butylperoxy 2-ethylhexyl monocarbonate, t-pentylperoxy 2-ethylhexyl monocarbonate, ethylhexyl monocarbonate, t-hexylperoxy 2-ethylhexyl monocarbonate, t-heptylperoxy 2-ethylhexyl monocarbonate, t-octylperoxy 2-ethylhexyl monocarbonate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexyl monocarbonate, diisobutyl peroxide, cumylperoxy neodecanoate, di-n-propylperoxydicarbonate, diisopropylperoxydicarbonate, di-sec-butylperoxydicarbonate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, bis(2-ethylhexyl)peroxydicarbonate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-butylperoxyneoheptanoate, t-hexylperoxypivalate, t-butylperoxypivalate, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, disuccinic acid peroxide, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy) Examples of organic peroxides include hexane, t-hexylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoylperoxide, t-butylperoxy-2-ethylhexylcarbonate, t-butylperoxyisopropylcarbonate, 1,6-bis(t-butylperoxycarbonyloxy)hexane, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyacetate, t-butylperoxybenzoate, t-amylperoxy, 3,5,5-trimethylhexanoate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, and 2,2-di-t-butylperoxybutane. The organic peroxides may be used alone or in combination of two or more.

[0043] Among these, t-butylperoxyisopropyl monocarbonate, t-pentylperoxyisopropyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy2-ethylhexyl monocarbonate, t-pentylperoxy2-ethylhexyl monocarbonate, t-hexylperoxy2-ethylhexyl monocarbonate, t-amylperoxyisopropyl monocarbonate, di-t-hexyl peroxide, t-butylperoxy2-ethylhexanoate, Preferred organic peroxides are t-butyl peroxyisobutyrate, t-hexylperoxy 2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy 2-ethylhexanoate, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate, because they can efficiently promote crosslinking of the resin that constitutes the resin particles.

[0044] Since the heating temperature during crosslinking treatment can be set low, the peroxide is preferably a compound exhibiting a one-hour half-life temperature of 200° C. or less, more preferably a compound exhibiting a one-hour half-life temperature of 170° C. or less, and even more preferably a compound exhibiting a one-hour half-life temperature of 140° C. or less. The lower limit of the one-hour half-life temperature of the peroxide may be 50° C. or more, 60° C. or more, or 70° C. or more.

[0045] Particularly preferred organic peroxides exhibiting such a one-hour half-life temperature are t-butylperoxyisopropylmonocarbonate, t-butylperoxy2-ethylhexylmonocarbonate, di-sec-butylperoxydicarbonate, t-butylperoxy2-ethylhexanoate, t-butylperoxyisobutyrate, t-hexylperoxy2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy2-ethylhexanoate, t-butylperoxypivalate, t-hexylperoxypivalate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, and 1,1,3,3-tetramethylbutylperoxyneodecanoate.

[0046] The case where the peroxide is an inorganic peroxide will be described. Examples of the inorganic peroxide include hydrogen peroxide, potassium peroxide, calcium peroxide, sodium peroxide, magnesium peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate, taking into consideration the heating temperature and / or time during crosslinking treatment. Among them, hydrogen peroxide, potassium persulfate, sodium persulfate, and ammonium persulfate are preferred in terms of ease of handling and having a decomposition temperature suitable for the heating temperature during crosslinking treatment. The inorganic peroxide may be used alone or in combination of two or more. An organic peroxide and an inorganic peroxide may be used in combination.

[0047] (polyfunctional compound) The crosslinked structure in the crosslinked resin particle (B) may be introduced by using only peroxide, but it is preferable that it is introduced by using both peroxide and polyfunctional compound. That is, it is preferable that the present crosslinked resin particle is crosslinked in the presence of peroxide and polyfunctional compound. When both peroxide and polyfunctional compound are used, it is possible to increase the gel fraction of the crosslinked resin particle (B) with a smaller amount of peroxide compared to the case where only peroxide is used.

[0048] The polyfunctional compound refers to a compound having two or more functional groups (e.g., radical reactive groups) in one molecule that can crosslink the resin (e.g., PHA) that constitutes the resin particles. The polyfunctional compound is not particularly limited, but is preferably a compound that is reactive with a radical generated from a peroxide, and is particularly preferably a compound having two or more radical reactive groups in one molecule. The radical reactive group is preferably at least one selected from the group consisting of a vinyl group, an allyl group, an acryloyl group, and a methacryloyl group.

[0049] Such polyfunctional compounds are not particularly limited, but examples thereof include allyl (meth)acrylate, allyl alkyl (meth)acrylates, allyloxy alkyl (meth)acrylates, polyfunctional (meth)acrylates having two or more (meth)acrylic groups, such as ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate, divinylbenzene, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Preferably, the compound is one or more selected from the group consisting of allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene, and more preferably, the compound is one or more selected from the group consisting of allyl methacrylate and triallyl isocyanurate.

[0050] When a crosslinked structure is formed in the presence of a polyfunctional compound, the resulting crosslinked resin particles (B) may usually contain a structure derived from the polyfunctional compound, in which case the molecular chains of the resin constituting the resin particles are bonded to each other via the structure derived from the polyfunctional compound.

[0051] (Other Ingredients) The crosslinked resin particles (B) are crosslinked resin particles containing PHA. Therefore, the crosslinked resin particles (B) may be crosslinked resin particles containing only PHA, or may be crosslinked resin particles containing other components other than PHA. Examples of the other components include resins other than PHA, antioxidants, hydrolysis inhibitors, antiblocking agents, crystal nucleating agents, lubricants, and ultraviolet absorbers.

[0052] The ratio of PHA in the crosslinked resin particles (B) is not particularly limited. The content of PHA in 100% by weight of the resin component of the crosslinked resin particles (B) may be 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, particularly preferably 95% by weight or more, and may be 99% by weight or more. The upper limit of the content of PHA in 100% by weight of the resin component of the crosslinked resin particles (B) is not particularly limited, and may be 100% by weight or less. Note that the "resin component of the crosslinked resin particles" refers to the resin that essentially constitutes the crosslinked resin particles, and does not include components that crosslink the molecular chains of the resin (for example, a structure derived from a polyfunctional compound) and residues of components used for crosslinking the molecular chains of the resin (for example, unreacted peroxide, decomposition product of peroxide, unreacted polyfunctional compound, etc.).

[0053] Examples of resins other than PHA include aliphatic polyesters other than PHA and aliphatic aromatic polyesters. Examples of aliphatic polyesters other than PHA include (i) polycaprolactone (PCL), (ii) polylactic acid (PLA), and (iii) aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed. Specific examples of the aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed include polyethylene succinate, polybutylene succinate (hereinafter sometimes referred to as "PBS"), polyhexamethylene succinate, polyethylene adipate, polybutylene adipate, polyhexamethylene adipate, polybutylene succinate adipate (hereinafter sometimes referred to as "PBSA"), polyethylene sebacate, polybutylene sebacate, etc. The aliphatic aromatic polyester includes an aliphatic aromatic polyester (both an aliphatic compound and an aromatic compound are used as monomers) obtained by copolymerizing the monomers using both an aliphatic compound and an aromatic compound. Examples of the aliphatic aromatic polyester include polybutylene adipate terephthalate (hereinafter sometimes referred to as "PBAT"), polybutylene sebacate terephthalate (hereinafter sometimes referred to as "PBSeT"), polybutylene azelate terephthalate (hereinafter sometimes referred to as "PBAzT"), polybutylene succinate terephthalate (hereinafter sometimes referred to as "PBST"), and polybutylene succinate adipate terephthalate (hereinafter sometimes referred to as "PBSAT"). These resins other than PHA may be used alone or in combination of two or more. In the crosslinked resin particles (B), the resins other than PHA may be crosslinked or not crosslinked.

[0054] The crosslinked resin particles (B) are different from the expanded resin particles disclosed in WO 2007 / 049694 and WO 2019 / 146555, and are preferably not expanded. In other words, the crosslinked resin particles (B) preferably do not substantially contain air bubbles inside the particles. "Substantially does not contain air bubbles inside the particles" means that the volume of air bubbles (spaces) is 10% or less in 100% of the volume of the crosslinked resin particles.

[0055] When the crosslinked resin particles (B) are not expanded, the apparent density of the crosslinked resin particles is relatively large. The apparent density of the crosslinked resin particles (B) is 0.6 g / cm 3 It is preferable that the density exceeds 0.7 g / cm 3 More preferably, it is 0.9 g / cm or more. 3 The apparent density of the crosslinked resin particles (B) can be determined by the method described in JIS K0061 (Method for measuring density and specific gravity of chemical products) or JIS Z8807 (Method for measuring density and specific gravity of solids).

[0056] The average weight per particle of the crosslinked resin particles (B) is not particularly limited. For example, when the volume average particle size of the crosslinked resin particles (B) is 10.00 μm or less, the average weight per particle of the crosslinked resin particles can be much less than 0.1 mg.

[0057] The crosslinked resin particles (B) may be dried. The shape of the dried particles may be powder, pellets, crumbs, a film, a sheet, or the like, depending on the drying method.

[0058] <Production method of crosslinked resin particles (B)> An example of a method for producing the crosslinked resin particles (B) will be specifically described. The crosslinked resin particles (B) can be produced by crosslinking the molecular chains of the resin in an aqueous dispersion containing resin particles before crosslinking treatment in the presence of a peroxide. The term "resin particles" refers to particles composed of a resin component that essentially constitutes the crosslinked resin particles. When the resin component is composed only of PHA, the resin particles can also be called PHA particles. In order to efficiently crosslink the molecular chains of the resin, it is preferable to heat the aqueous dispersion of the resin particles containing the peroxide to a temperature suitable for decomposing the peroxide.

[0059] More specifically, the method for producing the crosslinked resin particles (B) preferably includes the steps of: (1) preparing an aqueous dispersion of resin particles in which pre-crosslinked resin particles (e.g., PHA particles) are dispersed in water; (2) adding a peroxide to the aqueous dispersion of resin particles to impregnate the resin particles with the peroxide; and (3) heating the aqueous dispersion of resin particles impregnated with the peroxide to a heating temperature to crosslink the resin molecular chains (e.g., PHA molecular chains). It is more preferable to further include the step of (4) maintaining the heating temperature after all the peroxide has been added.

[0060] In step (1), for example, the aqueous dispersion of PHA particles may be an aqueous dispersion obtained by culturing a PHA-producing microorganism to accumulate PHA in the cells, and then disrupting the cells in the culture medium to separate and remove the cell components, or an aqueous dispersion obtained by concentrating or diluting the aqueous dispersion. According to such a method, the process from producing PHA particles by culturing a PHA-producing microorganism to crosslinking treatment can be carried out without separating the PHA particles from water.

[0061] Alternatively, an aqueous dispersion of resin particles (eg, PHA particles) can be prepared by dispersing dried resin particles (eg, PHA particles) in water.

[0062] The aqueous medium contained in the aqueous dispersion may be water alone or may be a mixed solvent of water and a water-compatible organic solvent. In the mixed solvent, the concentration of the water-compatible organic solvent is not particularly limited as long as it is equal to or lower than the solubility in water of the organic solvent used.

[0063] The organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; dimethyl sulfoxide; pyridine; piperidine; and the like. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, and the like are preferred because they are easily removed. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and the like are more preferred because they are easily available. Furthermore, methanol, ethanol, and acetone are particularly preferred.

[0064] The water content in the entire aqueous medium (100% by weight) constituting the aqueous dispersion is preferably 5% by weight to 100% by weight. The water content in 100% by weight of the aqueous medium is more preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more. The water content in 100% by weight of the aqueous medium may be 90% by weight or more, or may be 95% by weight or more.

[0065] In the aqueous dispersion, the volume average particle diameter of the resin particles is preferably within the same range as the volume average particle diameter of the above-mentioned crosslinked resin particles.In the case of the PHA particles produced by the PHA-producing microorganism, the volume average particle diameter can usually be within the above range, so that the aqueous dispersion of PHA particles having a desired volume average particle diameter can be obtained without carrying out a special process for adjusting the particle diameter.

[0066] The concentration of the resin particles in the aqueous dispersion is not particularly limited and can be set appropriately, but may be, for example, about 1 to 70% by weight, and preferably about 5 to 50% by weight.

[0067] The aqueous dispersion of resin particles preferably contains a dispersant in order to increase the dispersibility of the resin particles and to uniformly proceed with the crosslinking reaction. Examples of dispersants include anionic surfactants such as dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium lauryl sulfate, and sodium oleate; cationic surfactants such as lauryl trimethyl ammonium chloride; nonionic surfactants such as glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, and polyoxyethylene polyoxypropylene glycol; and water-soluble polymers such as polyvinyl alcohol, ethylene-modified polyvinyl alcohol, polyvinylpyrrolidone, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polymethacrylic acid, and sodium polymethacrylate. Only one of these dispersants may be used, or two or more of them may be used in combination.

[0068] When a dispersant is used, the content (addition amount) of the dispersant in the aqueous dispersion is not particularly limited. The content of the dispersant in the aqueous dispersion may be, for example, 0.1 to 10 parts by weight, preferably 0.5 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the resin particles.

[0069] In step (2), a peroxide is added to the aqueous dispersion of resin particles obtained in step (1) to impregnate the resin particles with the peroxide. The peroxide may be any of those mentioned above. Peroxide may be added in various forms, such as solid or liquid. Alternatively, a liquid form diluted with a diluent may be added. The peroxide may be added all at once, or may be added continuously or in portions.

[0070] When the peroxide and the polyfunctional compound are used in combination, it is preferable to add the polyfunctional compound to the aqueous dispersion of the resin particles in step (2). The polyfunctional compound can be any of those mentioned above. The polyfunctional compound can be added in various forms, such as solid or liquid. A liquid diluted with a diluent or the like may also be added. The polyfunctional compound may be added all at once, continuously, or in portions.

[0071] In step (2), the method of impregnating the resin particles with the peroxide and any polyfunctional compound may be such that, after or while adding these compounds to the aqueous dispersion of the resin particles, the temperature of the aqueous dispersion is set to, for example, 0°C or higher but lower than a temperature suitable for decomposing the peroxide employed in the next step (3), and the temperature is maintained, for example, for about 1 minute to 5 hours while stirring the aqueous dispersion. Specifically, the temperature of the aqueous dispersion during impregnation may be about 0°C to 80°C.

[0072] The amount of the peroxide used can be appropriately set in consideration of the gel fraction of the crosslinked resin particles. For example, the amount of the peroxide used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, further preferably 0.3 to 5 parts by weight, and particularly preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0073] According to a manufacturing method in which resin particles are crosslinked in an aqueous dispersion using a peroxide, crosslinking can be promoted while maintaining the particle size (volume) before crosslinking, and crosslinked resin particles can be easily obtained. On the other hand, in a method in which a resin is crosslinked by melt kneading in the presence of a peroxide, this can be difficult to achieve.

[0074] In addition, the manufacturing method in which resin particles are crosslinked in an aqueous dispersion using a peroxide has the advantage that it is easy to control the temperature increase caused by the heat generated during the crosslinking reaction, and crosslinked resin particles having a safe and stable crosslinked structure (quality) can be efficiently obtained.

[0075] The amount of the polyfunctional compound used may be appropriately set in consideration of the gel fraction of the crosslinked resin particles. The amount of the polyfunctional compound used is, for example, preferably 0.01 to 20 parts by weight, more preferably 0.05 to 15 parts by weight, even more preferably 0.1 to 10 parts by weight, even more preferably 0.2 to 5 parts by weight, and particularly preferably 0.3 to 3 parts by weight, relative to 100 parts by weight of the resin particles.

[0076] In step (3), the aqueous dispersion of resin particles impregnated with the peroxide is heated to a temperature suitable for decomposing the peroxide. The heating temperature is preferably within a range of about 25°C above and below the one-hour half-life temperature of the peroxide (one-hour half-life temperature -25°C to one-hour half-life temperature +25°C). Specifically, the heating temperature is preferably 30°C to 140°C, more preferably 50°C to 135°C, and even more preferably 60°C to 130°C. According to this method, it is possible to crosslink the resin at a temperature lower than the melting temperature of the resin (e.g., PHA), so that deterioration of the resin due to heating during the crosslinking treatment can be avoided. The melting temperature of PHA is, for example, 50°C to 210°C.

[0077] In the subsequent step (4), it is preferable to maintain the heating temperature. This allows the crosslinking reaction using the peroxide to proceed sufficiently. The time for maintaining the heating temperature is not particularly limited, but is preferably 1 minute to 15 hours, and more preferably 1 hour to 10 hours.

[0078] After the crosslinking reaction is completed, the crosslinked resin particles (B) are separated from the aqueous dispersion, and water is removed from the separated crosslinked resin particles (B) to obtain dried crosslinked resin particles (B). The method for separating the crosslinked resin particles (B) from the aqueous dispersion is not particularly limited, and for example, filtration, centrifugation, heat drying, freeze drying, spray drying, etc. can be used. For example, spray drying can be used to obtain dried crosslinked resin particles (B) directly from the aqueous dispersion. In addition, the crosslinked resin particles (B) can be extruded alone after separation from the aqueous dispersion, and the crosslinked resin particles (B) can be obtained in the form of pellets while completely removing the remaining moisture. In addition, a coagulation step using a coagulant and / or pH adjustment can be performed.

[0079] In the thermoplastic resin composition constituting the present injection molded product, the blending amount of the crosslinked resin particles (B) is 1 to 60 parts by weight in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). When the crosslinked resin particles (B) are used in the above range, the mechanical strength such as the impact strength of the thermoplastic resin (A) can be improved, and as a result, the impact resistance of the present injection molded product can also be improved. The content of the crosslinked resin particles (B) in the thermoplastic resin composition constituting the present injection molded product may be 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more in 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). The content of the crosslinked resin particles (B) in the thermoplastic resin composition constituting the present injection molded article is preferably 55 parts by weight or less, more preferably 53 parts by weight or less, and even more preferably 50 parts by weight or less, based on 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). The content of the crosslinked resin particles (B) in the thermoplastic resin composition constituting the present injection molded article may be 45 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 12 parts by weight or less, or 10 parts by weight or less, based on 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B).

[0080] <Thermoplastic resin (A)> In the thermoplastic resin composition constituting the present injection molded article, the thermoplastic resin (A) can also be called a matrix resin. The thermoplastic resin (A) is not particularly limited as long as it is a resin that can be molded into a desired shape by melting it by heating and then cooling and solidifying it. Specific examples of the thermoplastic resin (A) include polyolefin resins such as polyethylene and polypropylene, acrylic resins such as polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, polytetrafluoroethylene, and polymethyl methacrylic acid, AS resins, polyamides, polyacetals, polycarbonates, modified polyphenylene ethers, polyester resins, and cyclic polyolefins. These thermoplastic resins may be used alone or in combination of two or more. The thermoplastic resin preferably has a gel fraction of less than 50%. The thermoplastic resin is preferably not crosslinked.

[0081] As the thermoplastic resin (A), polyester-based resins are particularly preferred, such as aliphatic polyesters (e.g., PHA, PLA, PCL, and aliphatic polyesters having a structure in which an aliphatic diol and an aliphatic dicarboxylic acid are polycondensed, etc.) and aliphatic aromatic polyesters.

[0082] Specific embodiments of the aliphatic polyester and the aliphatic aromatic polyester are the same as those explained in the above sections on (PHA) and (Other Components), and therefore the explanations therefor are incorporated by reference and will not be repeated here.

[0083] Since the crosslinked resin particles (B) contain PHA having biodegradability, it is preferable that the thermoplastic resin (A) also contains a resin having biodegradability, i.e., a biodegradable resin. This configuration has the advantage that the biodegradability of the entire thermoplastic resin composition and the entire molded body of the thermoplastic resin composition can be increased. Therefore, when the thermoplastic resin (A) contains a biodegradable resin, it is expected to be useful as a thermoplastic resin composition that addresses the problem of plastic waste and is friendly to the global environment. In addition, when the thermoplastic resin (A) contains a biodegradable resin, the present resin composition and its molded body can suppress soil pollution due to disposal. This can contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 12 "Ensure sustainable consumption and production patterns." Furthermore, when the biodegradable resin (A) has marine decomposition in addition to soil decomposition, the resin composition and molded body containing the present crosslinked resin particles can suppress marine pollution in addition to suppressing soil pollution due to disposal.

[0084] Furthermore, when the crosslinked resin particles (B) contain a resin produced from a plant-derived raw material, from the viewpoint of resource circulation, it is preferable that the thermoplastic resin (A) also contains a resin produced from a plant-derived raw material, and it is more preferable that the thermoplastic resin (A) is composed only of a resin produced from a plant-derived raw material.

[0085] In the thermoplastic resin composition constituting the present injection molded body, the blending amount of the thermoplastic resin (A) is 40 parts by weight to 99 parts by weight relative to 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). When the thermoplastic resin (A) is used in the above range, the mechanical strength such as the impact strength of the thermoplastic resin (A) can be improved by the crosslinked resin particles (B), and as a result, the impact resistance of the present injection molded body can also be improved. The content of the thermoplastic resin (A) in the thermoplastic resin composition constituting the present injection molded body may be 40 parts by weight to 95 parts by weight, 45 parts by weight to 93 parts by weight, 47 parts by weight to 90 parts by weight, 50 parts by weight to 80 parts by weight, 50 parts by weight to 85 parts by weight, 50 parts by weight to 75 parts by weight, or 50 parts by weight to 70 parts by weight, relative to 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B). The content of the thermoplastic resin (A) in the thermoplastic resin composition constituting the present injection molded article may be 55 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 88 parts by weight or more, or 90 parts by weight or more, based on 100 parts by weight of the total of the thermoplastic resin (A) and the crosslinked resin particles (B).

[0086] The case where the thermoplastic resin (A) contains a biodegradable resin will be described. The thermoplastic resin (A) preferably contains 10% by weight to 100% by weight of a biodegradable resin in 100% by weight of the thermoplastic resin (A). The thermoplastic resin (A) more preferably contains 30% by weight or more of a biodegradable resin in 100% by weight of the thermoplastic resin (A), more preferably contains 50% by weight or more, even more preferably contains 70% by weight or more, and particularly preferably contains 90% by weight or more. The thermoplastic resin (A) may be composed of only a biodegradable resin.

[0087] Since the injection molded article can enjoy the impact resistance improvement effect of the crosslinked resin particles (B), the biodegradable resin preferably contains a polyester resin, more preferably contains an aliphatic polyester, and particularly preferably contains a PHA and / or polylactic acid. The PHA used as the thermoplastic resin (A) preferably has a gel fraction of less than 50%. The PHA used as the thermoplastic resin (A) preferably does not have a crosslinked structure.

[0088] The case where the thermoplastic resin (A) contains PHA and / or polylactic acid as a biodegradable resin will be described below. The thermoplastic resin (A) preferably contains 10% by weight to 100% by weight of PHA and polylactic acid in total, more preferably 30% by weight or more, even more preferably 50% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more, based on 100% by weight of the thermoplastic resin (A).

[0089] The PHA that can be used as the thermoplastic resin (A) is not particularly limited, and examples thereof include polyglycolic acid, P3HA, poly(4-hydroxyalkanoate) resins, etc. As the PHA, only one type may be used, or two or more types may be used in combination. As the PHA used as the thermoplastic resin (A), P3HA is particularly preferred.

[0090] A case where the crosslinked resin particles (B) contain P3HA and the thermoplastic resin (A) contains P3HA will be described. The P3HA that can be used as the thermoplastic resin (A) is the same as the P3HA related to the crosslinked resin particles (B), and the above-mentioned various P3HAs can be used. The P3HA contained in the thermoplastic resin (A) may be a resin having the same composition as the P3HA contained in the crosslinked resin particles (B), or may be a resin having a different composition and / or physical properties. The P3HA contained in the thermoplastic resin (A) is preferably a resin having a different composition and / or physical properties from the P3HA contained in the crosslinked resin particles (B), and is more preferably a resin harder than the P3HA contained in the crosslinked resin particles (B).

[0091] The case where the P3HA used as the thermoplastic resin (A) contains a 3-hydroxybutanoic acid (3HB) repeating unit will be described. In this case, from the viewpoint of the balance between flexibility and strength, the composition ratio of the 3HB repeating unit in the total monomer repeating units of P3HA (100 mol%) is preferably 80 mol% to 99 mol%, more preferably 82 mol% to 97 mol%. When the composition ratio of the 3HB repeating unit in P3HA is 80 mol% or more, the rigidity of P3HA can be improved. On the other hand, when the composition ratio of the 3HB repeating unit in P3HA is 99 mol% or less, the flexibility of P3HA tends to be improved. As P3HA, two or more types having different composition ratios of the 3HB repeating unit may be used in combination.

[0092] The weight average molecular weight of the PHA used as the thermoplastic resin (A) is not particularly limited, but is preferably 50,000 to 3,000,000, more preferably 100,000 to 2,000,000, and even more preferably 150,000 to 1,500,000. When the weight average molecular weight of the PHA is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present injection molded article. On the other hand, a PHA having a weight average molecular weight of 3,000,000 or less may have the advantage that the PHA is easy to manufacture and / or that the PHA is easy to handle in order to achieve the object of one embodiment of the present invention.

[0093] Polylactic acid usable as the thermoplastic resin (A) may be any conventionally known polylactic acid. The polylactic acid may be crystalline polylactic acid, amorphous polylactic acid, or a mixture of crystalline polylactic acid and amorphous polylactic acid.

[0094] The polylactic acid may be a homopolymer of lactic acid, a copolymer of lactic acid and other monomers, or a blend of a homopolymer of lactic acid and a copolymer of lactic acid and other monomers.

[0095] Examples of the other monomers include aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides.

[0096] The lactic acid raw material for producing polylactic acid is not particularly limited, and L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, or L-lactide, D-lactide, meso-lactide, or a mixture thereof, etc. can be used. Lactic acid obtained by microbial fermentation from renewable raw materials derived from plants such as starch can be preferably used. The method for producing polylactic acid is not particularly limited, and known methods such as dehydration condensation polymerization and ring-opening polymerization can be applied.

[0097] The weight average molecular weight of the polylactic acid (A) used as the thermoplastic resin (A) is not particularly limited, but is preferably 50,000 to 1,000,000, more preferably 70,000 to 700,000, and even more preferably 100,000 to 400,000. When the weight average molecular weight of the polylactic acid is 50,000 or more, sufficient rigidity and / or strength can be obtained in the present injection molded article. On the other hand, polylactic acid having a weight average molecular weight of 1,000,000 or less may have the advantage that the polylactic acid is easy to produce and / or easy to handle in order to achieve the object of one embodiment of the present invention.

[0098] Regarding the PHA used as the thermoplastic resin (A), other aspects than those described above are the same as those explained in the section on (PHA), so the explanation therefor is incorporated by reference and will not be repeated here.

[0099] <Nucleating agent> The thermoplastic resin composition may further contain a crystal nucleating agent. When the thermoplastic resin (A) is a crystalline resin, the inclusion of the crystal nucleating agent in the thermoplastic resin composition promotes crystallization during molding, and molding processability, productivity, etc. can be improved. When the thermoplastic resin composition contains a crystal nucleating agent, there is also an advantage that a thermoplastic resin composition having excellent heat resistance or mechanical properties and an injection molded article thereof can be obtained.

[0100] The crystal nucleating agent is not particularly limited, and conventionally known ones can be used. Examples of the crystal nucleating agent include inorganic substances such as talc, kaolinite, montmorillonite, mica, synthetic mica, clay, zeolite, silica, carbon black, graphite, boron nitride, zinc oxide, titanium oxide, tin oxide, calcium carbonate, magnesium carbonate, aluminum oxide, neodymium oxide, barium sulfate, sodium chloride, and metal phosphates; sugar alcohol compounds derived from natural products such as erythritol, pentaerythritol, galactitol, mannitol, and arabitol; polysaccharides such as chitin and chitosan; polyols such as aliphatic alcohols (polyols), polyvinyl alcohol, and polyethylene oxide; sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, potassium terephthalate, calcium oxalate, sodium laurate, potassium laurate, and sodium myristate. metal salts of organic carboxylic acids such as ammonium, potassium myristate, calcium myristate, sodium octacosanoate, calcium octacosanoate, sodium stearate, potassium stearate, lithium stearate, calcium stearate, magnesium stearate, barium stearate, sodium montanate, calcium montanate, sodium toluate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalate, and sodium cyclohexanecarboxylate; organic sulfonates such as sodium p-toluenesulfonate and sodium sulfoisophthalate; carboxylic acid amides such as ethylene stearamide, ethylene bislaurate, palmitic acid amide, hydroxystearamide, erucic acid amide, and trimesic acid tris(t-butylamide);Lauric acid ester, palmitic acid ester, oleic acid ester, stearic acid ester, erucic acid ester, N-oleyl palmitic acid ester, N-oleyl oleic acid ester, N-oleyl stearate ester, N-stearyl oleic acid ester, N-stearyl stearate ester, N-stearyl erucic acid ester, methylene bisstearate ester, ethylene bislaurate ester, ethylene biscaprate ester, ethylene bisoleic acid ester, ethylene bisstearate ester, ethylene biserucate ester, ethylene bisisostearate ester, butylene bisstearate ester, p-xylylene bisstearyl Examples of the nucleating agent include carboxylate esters such as phosphate esters; dicarboxylic acid derivatives such as dimethyl adipate, dibutyl adipate, diisodecyl adipate, and dibutyl sebacate; cyclic compounds having a functional group C=O and one or more functional groups selected from the group consisting of NH, S, and O in the molecule, such as indigo, quinacridone, and quinacridone magenta; sorbitol derivatives such as bisbenzylidene sorbitol and bis(p-methylbenzylidene) sorbitol; compounds containing a nitrogen-containing heteroaromatic nucleus such as pyridine, triazine, and imidazole; phosphate ester compounds, bisamides of higher fatty acids, and metal salts of higher fatty acids; branched polylactic acid; and low molecular weight poly(3-hydroxybutyrate). These crystal nucleating agents may be used alone or in combination of two or more.

[0101] The content of the crystal nucleating agent is not particularly limited as long as it can promote the crystallization of the thermoplastic resin (A). The content of the crystal nucleating agent is preferably 0.05 parts by weight to 12.00 parts by weight, more preferably 0.10 parts by weight to 10.00 parts by weight, and even more preferably 0.50 parts by weight to 8.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin (A). When the content of the crystal nucleating agent is within the above range, the effect of the crystal nucleating agent can be obtained while suppressing the decrease in viscosity during molding and the physical properties of the injection molded article.

[0102] <Lubricant> The thermoplastic resin composition may further contain a lubricant. When the thermoplastic resin composition contains a lubricant, the surface smoothness of the obtained injection molded article can be improved. The lubricant is not particularly limited. Examples of the lubricant include, but are not limited to, fatty acid metal salts such as magnesium stearate and calcium stearate; fatty acid amides such as behenic acid amide, stearic acid amide, erucic acid amide, oleic acid amide, methylene bisstearic acid amide, and ethylene bisstearic acid amide; polyethylene wax, oxidized polyester wax, glycerin monostearate, glycerin monobehenate, and glycerin monolaurate, and other glycerin monofatty acid esters; organic acid monoglycerides such as succinic acid saturated fatty acid monoglycerides; sorbitan fatty acid esters such as sorbitan behenate, sorbitan stearate, and sorbitan laurate; polyglycerin fatty acid esters such as diglycerin stearate, diglycerin laurate, tetraglycerin stearate, tetraglycerin laurate, decaglycerin stearate, and decaglycerin laurate; and higher alcohol fatty acid esters such as stearyl stearate. The lubricant may be used alone or in combination of two or more.

[0103] The content of the lubricant (when a plurality of lubricants are used, the total content thereof) is not particularly limited as long as it can impart lubricity to the molded body. The content of the lubricant is preferably 0.01 to 20.00 parts by weight, more preferably 0.05 to 10.00 parts by weight, even more preferably 0.10 to 10.00 parts by weight, even more preferably 0.20 to 5.00 parts by weight, and particularly preferably 0.30 to 4.00 parts by weight, relative to 100 parts by weight of the thermoplastic resin (A). When the content of the lubricant is within the above range, it is possible to obtain the effect of the lubricant while avoiding the bleeding out of the lubricant onto the surface of the injection molded body.

[0104] <Other ingredients> The thermoplastic resin composition constituting the present injection molded article may contain other components, such as plasticizers, organic fillers, inorganic fillers, antioxidants, hydrolysis inhibitors, ultraviolet absorbers, colorants such as dyes and pigments, and antistatic agents, to the extent that the functions of the obtained molded article are not impaired.

[0105] The plasticizer is not particularly limited. Examples of the plasticizer include polyester-based plasticizers such as polypropylene glycol sebacate ester, aliphatic dibasic acid ester-based plasticizers such as di-1-butyl adipate, di-n-butyl sebacate, and di-2-ethylhexyl azelate, glycerin-based plasticizers such as glycerin diacetomonolaurate, glycerin diacetomonocaprylate, and glycerin diacetomonodecanoate, polycarboxylic acid ester-based plasticizers such as tri-2-ethylhexyl acetyl citrate and tributyl acetyl citrate, and polyamide-based plasticizers such as polyethylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) block and / or random copolymers, and polytetramethylene glycol. Examples of the plasticizer include alkylene glycol-based plasticizers, phosphoric acid ester-based plasticizers such as diphenyl-2-ethylhexyl phosphate and diphenyloctyl phosphate, epoxy-based plasticizers such as epoxidized soybean oil and epoxidized linseed oil fatty acid butyl ester, and castor oil-based plasticizers such as castor oil fatty acid esters, methyl ricinoleate, ethyl ricinoleate, isopropyl ricinoleate, butyl ricinoleate, ethylene glycol monoricylate, propylene glycol monoricylate, trimethylolpropane monoricylate, sorbitan monoricylate, castor oil fatty acid polyethylene glycol ester, castor oil ethylene oxide adduct, castor oil-based polyol, castor oil-based toluol, and castor oil-based diol. These plasticizers may be used alone or in combination of two or more.

[0106] The organic filler is not particularly limited. Examples of the organic filler include fillers made of naturally derived materials such as wood-based materials (e.g., wood chips, wood flour, sawdust, etc.), rice husks, rice flour, starch, corn starch, rice straw, wheat straw, and natural rubber; organic fibers such as natural vegetable fibers, natural animal fibers, and synthetic fibers; and fillers made of synthetic resin materials such as polyester, polyacrylic, polyamide, nylon, polyethylene, polyolefin, polyvinyl alcohol, polyvinyl chloride, polyurethane, polyacetal, aramid, PBO (poly-p-phenylene benzobisoxazole), polyphenylene sulfide, acetyl cellulose, polybenzazole, polyarylate, polyvinyl acetate, and synthetic rubber.

[0107] The plant-derived natural fibers are not particularly limited. Examples of the plant-derived natural fibers include kenaf fiber, abaca fiber, bamboo fiber, jute fiber, hemp fiber, linen fiber, henequen (sisal), ramie fiber, hemp, cotton, banana fiber, coconut fiber, palm, paper mulberry, mitsumata, bagasse, etc. In addition, regenerated fibers such as pulp, cellulose fiber, and rayon processed from plant fibers are also included. Examples of the animal-derived natural fibers include wool, silk, cashmere, and mohair.

[0108] The inorganic filler is not particularly limited. Examples of the inorganic filler include silica-based inorganic fillers (e.g., quartz, fumed silica, silicic anhydride, fused silica, crystalline silica, amorphous silica, fillers obtained by condensing alkoxysilanes, ultrafine amorphous silica, etc.), alumina, zircon, iron oxide, zinc oxide, titanium oxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, glass, silicone rubber, silicone resin, titanium oxide, carbon fiber, mica, graphite, carbon black, ferrite, graphite, diatomaceous earth, white clay, clay, talc, calcium carbonate, manganese carbonate, magnesium carbonate, barium sulfate, silver powder, etc. These inorganic fillers may be surface-treated to increase dispersibility in the resin composition. In addition, these inorganic fillers may be used alone or in combination of two or more.

[0109] The antioxidant is not particularly limited. Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. These antioxidants may be used alone or in combination of two or more.

[0110] The hydrolysis inhibitor is not particularly limited. Examples of the hydrolysis inhibitor include carbodiimide compounds, epoxy compounds, isocyanate compounds, and oxazoline compounds. These hydrolysis inhibitors may be used alone or in combination of two or more.

[0111] The ultraviolet absorbing agent is not particularly limited. Examples of the ultraviolet absorbing agent include benzophenone compounds, benzotriazole compounds, triazine compounds, salicylic acid compounds, cyanoacrylate compounds, and nickel complex compounds. These ultraviolet absorbing agents may be used alone or in combination of two or more.

[0112] The coloring agent such as the pigment or dye is not particularly limited. Examples of the coloring agent include inorganic coloring agents such as titanium oxide, calcium carbonate, chromium oxide, cuprous oxide, calcium silicate, iron oxide, carbon black, graphite, titanium yellow, and cobalt blue; soluble azo pigments such as lake red, lithol red, and brilliant carmine; insoluble azo pigments such as dinitrile orange and fast yellow; phthalocyanine pigments such as monochlorophthalocyanine blue, polychlorophthalocyanine blue, and polybromophthalocyanine green; condensed polycyclic pigments such as indigo blue, perylene red, isoindolinone yellow, and quinacridone red; and dyes such as oracet yellow. These coloring agents may be used alone or in combination of two or more.

[0113] The antistatic agent is not particularly limited. Examples of the antistatic agent include low molecular weight antistatic agents such as fatty acid ester compounds, aliphatic ethanolamine compounds, and aliphatic ethanolamide compounds, and polymeric antistatic agents. These antistatic agents may be used alone or in combination of two or more.

[0114] The thermoplastic resin composition constituting the present injection molded article may contain any of the following additives: catalyst deactivators (hindered phenol compounds, thioether compounds, vitamin compounds, triazole compounds, polyamine compounds, hydrazine derivative compounds, phosphorus compounds, etc.), release agents (montanic acid and its salts, its esters, its half esters, stearyl alcohol, stearamide, polyethylene wax, etc.), color inhibitors (phosphites, hypophosphites, etc.), silane coupling agents (epoxy silane coupling agents, amino silane coupling agents, (meth)acrylic silane coupling agents, isocyanate silane coupling agents, etc.), flame retardants (red phosphorus, phosphate esters, brominated polystyrene, brominated polyphenylene ether, etc.), and the like. The resin composition may also contain, for example, polyethers, brominated polycarbonates, aluminum hydroxide, magnesium hydroxide, melamine and cyanuric acid or salts thereof, silicon compounds, etc.), conductive agents (carbon black, etc.), sliding improvers (graphite, fluororesins, etc.), epoxy compounds (glycidyl ether compounds, glycidyl ester compounds, polymer compounds grafted or copolymerized with glycidyl compounds, etc.), acid anhydride compounds (maleic anhydride, succinic anhydride, polymer compounds grafted or copolymerized with acid anhydrides, etc.), carbodiimide compounds (N,N'-di-2,6-diisopropylphenylcarbodiimide, 2,6,2',6'-tetraisopropyldiphenylcarbodiimide, polycarbodiimide, etc.), etc.

[0115] The content of each of the other components described above is not particularly limited as long as the effect of one embodiment of the present invention is exhibited, and can be appropriately set by a person skilled in the art.

[0116] <Method of producing thermoplastic resin composition> The thermoplastic resin composition constituting the present injection molded article can be produced by a known method. Specifically, the thermoplastic resin (A), the crosslinked resin particles (B), and optional components such as a crystal nucleating agent, a lubricant, and other components are melt-kneaded using an extruder, a kneader, a Banbury mixer, a kneading roll, or the like. When melt-kneading, it is preferable to mix while paying attention to the decrease in molecular weight due to thermal decomposition. The thermoplastic resin composition can also be produced by dissolving all the raw materials (components) in a soluble solvent and then removing the solvent.

[0117] When producing a thermoplastic resin composition by melt kneading, each component may be individually charged into an extruder, etc., or each component may be mixed in advance and the resulting mixture may be charged into an extruder, etc. For example, after mixing an aqueous dispersion of the thermoplastic resin (A) with an aqueous dispersion of the crosslinked resin particles (B), the resulting mixture may be dried in a dryer to obtain a mixed powder, and the mixed powder may be charged into an extruder, etc.

[0118] When melt kneading is performed using an extruder, the obtained thermoplastic resin composition may be extruded from the extruder into a strand shape and then cut, thereby processing the thermoplastic resin composition into particle shapes such as a bar shape, a cylinder shape, an elliptical cylinder shape, a sphere shape, a cube shape, a rectangular prism shape, or the like.

[0119] The resin temperature during melt kneading cannot be generally defined because it depends on the melting point and melt viscosity of the resin used, etc. The resin temperature during melt kneading is preferably 140°C to 250°C, more preferably 150°C to 230°C, and even more preferably 160°C to 210°C, from the viewpoint of uniformly dispersing the crosslinked resin particles (B) in the thermoplastic resin (A) while avoiding thermal decomposition of the thermoplastic resin (A).

[0120] <Elmendorf tear strength> The thermoplastic resin composition constituting the present injection molded article has an Elmendorf tear strength of 5 N / mm or more, preferably 10 N / mm or more, and more preferably 15 N / mm or more, as measured by the methods shown in (1) to (4) below. (1) The thermoplastic resin composition is molded into a sheet having a thickness of 110 μm to obtain a press sheet. (2) The press sheet obtained in step (1) is aged under conditions of 23° C. and 50% RH for 7 days to obtain a film sample. (3) The film sample obtained in step (2) is subjected to measurement of tear strength (unit: N) according to the Elmendorf tear method specified in JIS K7128-2. (4) The tear strength measured in (3) is divided by the thickness (unit: mm) of the film sample to calculate the Elmendorf tear strength.

[0121] Here, when the mechanical strength of the thermoplastic resin composition itself is high, the mechanical strength such as the Elmendorf tear strength is improved in the film sample made of the thermoplastic resin composition. Therefore, the Elmendorf tear strength being a large value of 5 N / mm or more means that the mechanical strength of the thermoplastic resin composition itself is high. When the mechanical strength of the thermoplastic resin composition itself is high, the mechanical strength such as impact resistance is also improved in the injection molded article obtained by molding the thermoplastic resin composition. Therefore, since the Elmendorf tear strength of the thermoplastic resin composition constituting the present injection molded article is a large value of 5 N / mm or more, the present injection molded article has excellent impact resistance.

[0122] The Elmendorf tear strength of the thermoplastic resin composition constituting the present injection molded article is usually 500 N / mm or less, and preferably 300 N / mm or less.

[0123] Specifically, the step (1) is carried out by pressing the thermoplastic resin composition into a sheet using a press. As an example, more specifically, the temperature of the part of the press that contacts the thermoplastic resin composition is adjusted to, for example, 165°C, and the pressure applied to the thermoplastic resin composition and the time for applying the pressure are appropriately adjusted so that the thermoplastic resin composition is in a sheet shape with a thickness of 110 μm, and the step (1) is carried out. The press is not particularly limited, and a commercially available press can be used. In addition, in the step (1), the temperature of the part of the press that contacts the thermoplastic resin composition may be appropriately set within a range in which the thermoplastic resin composition can be molded according to the thermoplastic resin (A) contained in the thermoplastic resin composition, and is not particularly limited. The temperature of the part of the press that contacts the thermoplastic resin composition has almost no effect on the Elmendorf tear strength of the obtained molded product, unless the temperature is so severe that the thermoplastic resin composition is significantly deteriorated. Therefore, when considering the Elmendorf tear strength of the molded product, the temperature of the part of the press that contacts the thermoplastic resin composition can be ignored.

[0124] In the step (2), the method of curing the press sheet is not particularly limited, and a known method can be adopted. The curing stabilizes the internal state of the obtained film sample, improving the accuracy of the measured tear strength. As a result, when the Elmendorf tear strength is calculated for each of a plurality of thermoplastic resin compositions having the same configuration, the calculated values ​​of the Elmendorf tear strength are approximately the same. In other words, by performing the curing, the Elmendorf tear strength becomes a value that reflects the configuration of the thermoplastic resin composition to be measured with high accuracy. Therefore, the Elmendorf tear strength being a large value of 5 N / mm or more means that the configuration of the thermoplastic resin composition is such that the mechanical strength of the thermoplastic resin composition itself is sufficiently high.

[0125] When measuring the tear strength in the step (3), a known device for measuring tear strength can be used. For example, a tear tester having functions and a structure conforming to the standard Elmendorf tear tester specified in JIS K7128-2 can be used.

[0126] [1-2. Injection molded product] <Physical properties of injection molded products> The injection molded article has excellent impact resistance. Here, excellent impact resistance means, for example, a Charpy impact strength of 5 kJ / m 2 More than 10 kJ / m 2 More preferably, 15 kJ / m 2 This means that the Charpy impact strength is equal to or greater than the above. The Charpy impact strength can be measured by the method described in the Examples. The cylinder temperature and mold temperature during the production of the injection molded article have almost no effect on the Charpy impact strength of the resulting injection molded article, unless the temperature is so severe that the thermoplastic resin composition is significantly deteriorated. Therefore, when considering the Charpy impact strength of the injection molded article, the cylinder temperature and mold temperature during the production of the injection molded article can be ignored.

[0127] The shape of the present injection molded body can be appropriately set according to the application, and is not particularly limited. The shape of the present injection molded body can be controlled by appropriately adjusting the shape of the mold used in the manufacturing method of the present injection molded body described later. Examples of the shape of the present injection molded body include a sheet shape, a rectangular parallelepiped shape, the shape of parts and components of home appliances or automobiles, the shape of various daily necessities themselves, or the shape of parts of the daily necessities, a container shape, a cap shape, a cup shape, and a bottle shape. In addition, the shape of the present injection molded body may be a shape having a cavity inside, or a shape having a hole.

[0128] Injection molded articles are usually formed in a mold and are produced by being removed from the mold. In this case, if the mold releasability is poor, a part of the formed injection molded article may remain in the mold, and the injection molded article produced may be a defective product with a deformed shape and / or cracks and wrinkles. On the other hand, the present injection molded article has excellent mold releasability as described above, and therefore can suitably prevent the injection molded article produced from being a defective product.

[0129] The thermoplastic resin composition of the injection molded body has high mechanical strength and excellent impact resistance. Therefore, even if the thickness is thinner than that of a general injection molded body, it is difficult to break when an impact is applied from the outside. Therefore, even if the thickness of the thinnest part of the injection molded body of the present invention is so thin that it cannot be used as a product in a general injection molded body, the injection molded body of the present invention can ensure impact resistance and be suitably used as a product. From the above, the thickness of the thinnest part of the injection molded body of the present invention may be 2 mm or less, preferably 1 mm or less, and more preferably 0.5 μm or less. In addition, from the viewpoint of ensuring its strength, the thickness of the thinnest part of the injection molded body of the present invention may usually be 0.2 mm or more, preferably 0.3 mm or more, and more preferably 0.4 μm or more.

[0130] <Applications of injection molded products> The use of the injection molded body of the present invention can be a general use of an injection molded body, and is not particularly limited. The injection molded body of the present invention is also excellent in impact resistance. Furthermore, since the injection molded body of the present invention has excellent mold releasability, it is preferably prevented from becoming a defective product, and as a result, it is also excellent in productivity. In addition, since the injection molded body of the present invention has excellent bleed-out resistance, bleed-out does not occur, and the appearance quality is also excellent. Therefore, the injection molded body of the present invention can be suitably used in applications where impact resistance, productivity, and appearance quality are required.

[0131] Specific applications of the injection molded article include, for example, containers, home appliance components, and vehicle components. Examples of the containers include packaging containers for liquid daily necessities such as hair washes, hair toners, cosmetics, detergents, and disinfectants; food packaging containers for liquids such as soft drinks, water, and seasonings; food packaging containers (dessert cups) for solids such as jellies, puddings, and yogurt; packaging containers for other medicines; and packaging containers for industrial liquids. Examples of the home appliance components include components for home appliances such as air conditioners, induction cooking heaters, washing machines, and dishwashers.

[0132] 2. Manufacturing method of injection molded body A manufacturing method for an injection molded body according to one embodiment of the present invention (hereinafter also referred to as "this manufacturing method") is a method for manufacturing the injection molded body, and includes an injection step of injecting the thermoplastic resin composition into a mold, a cooling step of cooling and solidifying the thermoplastic resin composition inside the mold that has been injected in the injection step to form an injection molded body, and an ejection step of ejecting the injection molded body obtained in the cooling step from inside the mold.

[0133] The present production method can produce the present injection molded article, that is, an injection molded article that has excellent impact resistance as well as excellent mold releasability and bleed-out resistance.

[0134] Each step constituting this manufacturing method will be described below.

[0135] <Injection process> The injection step in this manufacturing method is a step of injecting a thermoplastic resin composition into the inside of a mold. In detail, the injection step is a step of heating the thermoplastic resin composition to a predetermined temperature to make it in a molten state, applying a predetermined pressure to the thermoplastic resin composition in the molten state, and injecting the thermoplastic resin composition in the molten state into the inside of the mold to fill the inside of the mold.

[0136] The device used in the injection step is not particularly limited as long as it has a function of heating the thermoplastic resin composition to make it in a molten state and a function of applying pressure to the thermoplastic resin composition in the molten state to inject it into the inside of a mold. For example, a commercially available injection molding machine can be used as the device used in the injection step.

[0137] For the thermoplastic resin composition used in the injection step, the above description regarding the thermoplastic resin composition constituting the present injection molded article is incorporated herein by reference.

[0138] In addition, when the water content of the thermoplastic resin composition to be injected is low, it is possible to prevent the thermoplastic resin from being decomposed by hydrolysis during injection molding, and to prevent the physical properties of the thermoplastic resin composition and the injection molded article from being deteriorated. For this reason, it is preferable that the water content of the thermoplastic resin composition constituting the present injection molded article is low, and specifically, it is preferably 1.5% by weight or less, more preferably 1.0% by weight or less, based on the weight of the entire thermoplastic resin composition. In addition, the water content of the thermoplastic resin composition constituting the present injection molded article can usually be 0% by weight or more, preferably 0.01% by weight or more, based on the weight of the entire thermoplastic resin composition. The method for controlling the water content of the present thermoplastic resin composition is not particularly limited, and can be, for example, a method in the step of reducing the water content of the thermoplastic resin composition described later.

[0139] In the injection step, the temperature of the thermoplastic resin composition injected into the mold (hereinafter referred to as "injection temperature") is not particularly limited as long as it is a temperature at which the thermoplastic resin composition is in a molten state. In addition, when the injection temperature is higher, the thermoplastic resin composition tends to be in a suitable molten state, specifically, in a molten state with low viscosity. The thermoplastic resin composition in a molten state with low viscosity can be suitably injected into the mold and suitably filled into the mold, thereby improving the productivity of the present manufacturing method. From the viewpoint of improving the above-mentioned productivity, the injection temperature is preferably 150°C or higher, more preferably 155°C or higher, and even more preferably 160°C or higher. On the other hand, when the injection temperature is excessively high, the thermoplastic resin composition may decompose and / or the device used in the injection step may be damaged. From the viewpoint of preventing decomposition of the thermoplastic resin composition and damage to the device used in the injection step, the injection temperature is preferably 250°C or less, more preferably 230°C or less, and even more preferably 210°C or less.

[0140] In the injection step, the pressure applied to the thermoplastic resin composition when it is injected into the mold (hereinafter also referred to as "injection pressure") is not particularly limited as long as the thermoplastic resin composition can be injected into the mold. When the injection temperature is higher, the thermoplastic resin composition in the molten state can be suitably injected into the mold and suitably filled into the mold, thereby improving the productivity of the present manufacturing method. From the viewpoint of improving the above-mentioned productivity, the injection pressure is preferably 10 MPa or more, more preferably 20 MPa or more, and even more preferably 30 MPa or more. On the other hand, when the injection pressure is excessively high, the device used in the injection step and / or the mold may be damaged. From the viewpoint of preventing damage to the device used in the injection step and the mold, the injection pressure is preferably 200 MPa or less, more preferably 150 MPa or less, and even more preferably 120 MPa or less.

[0141] The shape of the mold used in the injection step may be changed according to the shape of the desired injection molded article. The material of the mold is not particularly limited as long as it is a material that does not break and / or deform under the conditions of injection temperature and injection pressure. For example, the material of the mold may be steel having a certain durability and heat resistance.

[0142] <Cooling process> The cooling step in this manufacturing method is a step of cooling and solidifying the thermoplastic resin composition in the mold that has been injected in the injection step, to form an injection molded article.

[0143] In the cooling step, the thermoplastic resin composition in the mold is cooled and solidified to form an injection molded body (hereinafter also referred to as the "cooling method"), and a known method can be adopted and is not particularly limited. As the cooling method, for example, in the injection step, a method of adjusting the temperature of the mold before the thermoplastic resin composition is injected into the inside to a temperature lower than the temperature of the thermoplastic resin composition in the molten state, etc. can be mentioned. The temperature of the mold before the thermoplastic resin composition is injected into the inside is not particularly limited as long as it is a temperature at which the thermoplastic resin composition in the mold can be cooled and solidified to form an injection molded body. It is preferable that the temperature of the mold before the thermoplastic resin composition is injected into the inside is low so that the thermoplastic resin composition in the mold can be suitably cooled and solidified to form an injection molded body. From the viewpoint of suitably cooling and solidifying the thermoplastic resin composition in the mold as described above to suitably form an injection molded body, the temperature of the mold before the thermoplastic resin composition is injected into the inside is specifically preferably 130 ° C or less, more preferably 120 ° C or less, and even more preferably 110 ° C or less. In addition, in view of the cost required to control the temperature of the mold, the temperature of the mold before the thermoplastic resin composition is injected therein is preferably 10°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher.

[0144] The cooling time in the cooling step is not particularly limited as long as the thermoplastic resin composition in the mold can be cooled and solidified to form an injection molded body. The cooling time means the time from the start of injection of the thermoplastic resin composition into the mold in the injection step to the time when the injection molded body formed in the cooling step is removed from the mold, that is, the time until the start of the removal step. The cooling time is not particularly limited and can be appropriately adjusted according to the shape of the injection molded body to be produced and the composition of the thermoplastic resin composition used, such as the type of thermoplastic resin (A).

[0145] In the cooling step, in order to eliminate the resin shortage caused by the shrinkage of the thermoplastic resin composition due to cooling and to avoid adverse effects on the appearance and / or size of the injection-molded article produced, it is preferable to carry out a dwelling process in which a certain pressure is applied to the thermoplastic resin composition in the mold. The pressure in the dwelling process is not particularly limited, and can be appropriately adjusted according to the shape of the injection-molded article produced and the composition of the thermoplastic resin composition used, for example, the type of thermoplastic resin (A), etc.

[0146] In the cooling step, it is preferable to maintain the temperature of the mold at the temperature before the thermoplastic resin composition is injected therein by using cooling water, hot water, etc. This makes it possible to more suitably cool and solidify the thermoplastic resin composition in the mold, thereby suitably forming an injection-molded article.

[0147] <Removal process> In the removal step of this production method, the method for removing the injection molded article obtained in the cooling step from the mold is not particularly limited, and any known method can be used.

[0148] <Thermoplastic resin composition preparation process> The present production method may include a thermoplastic resin composition preparation step of preparing a thermoplastic resin composition as a raw material. The thermoplastic resin composition preparation step may employ the above-mentioned method for producing the thermoplastic resin composition constituting the present injection molded article.

[0149] <Step of reducing the moisture content of the thermoplastic resin composition> The present manufacturing method may include a step of reducing the moisture content of the thermoplastic resin composition before the injection step. As a method for reducing the moisture content of the thermoplastic resin composition, a known method for reducing the moisture content, i.e., a known drying method, can be adopted, and is not particularly limited. As a method for reducing the moisture content of the thermoplastic resin composition, for example, a method for reducing the moisture content of the thermoplastic resin composition by applying a predetermined drying temperature for a predetermined drying time can be mentioned. The drying temperature and the drying time can be appropriately adjusted depending on the moisture content of the thermoplastic resin composition to be subjected to the step of reducing the moisture content of the thermoplastic resin composition, i.e., the thermoplastic resin composition before drying. The drying temperature is, for example, 40°C to 120°C, preferably 50°C to 110°C, and more preferably 60°C to 100°C. The drying time is, for example, 10 minutes to 50 hours, preferably 20 minutes to 40 hours, and more preferably 30 minutes to 30 hours.

[0150] <Curing process> The present manufacturing method may include a curing step of curing the injection molded body obtained in the removal step. In detail, the curing step is a step of curing the injection molded body by leaving the injection molded body obtained in the removal step under conditions of a predetermined temperature and a predetermined humidity for a predetermined time. The curing step is preferable in terms of stabilizing the internal structure of the injection molded body and controlling the physical properties within a suitable range. In addition, when evaluating the physical properties of the injection molded body, stable physical property data can be obtained by performing the curing step, and more stable evaluation is possible. The conditions such as temperature, humidity, and time in the curing step are not particularly limited and can be appropriately adjusted according to the final use and purpose of the injection molded body.

[0151] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.

[0152] That is, one embodiment of the present invention includes the following inventions. <1> An injection molded article obtained by molding a thermoplastic resin composition, The thermoplastic resin composition comprises 40 to 99 parts by weight of a thermoplastic resin (A) and 1 to 60 parts by weight of crosslinked resin particles (B) (wherein the total amount of (A) and (B) is 100 parts by weight), The crosslinked resin particles (B) contain a polyhydroxyalkanoate resin and have a gel fraction of 50% or more, The thermoplastic resin composition has an Elmendorf tear strength of 5 N / mm or more as measured by the following methods (1) to (4): (1) The thermoplastic resin composition is molded into a sheet having a thickness of 110 μm to obtain a press sheet. (2) The press sheet obtained in step (1) is aged under conditions of 23° C. and 50% RH for 7 days to obtain a film sample. (3) The film sample obtained in step (2) is subjected to measurement of tear strength (unit: N) according to the Elmendorf tear method specified in JIS K7128-2. (4) The tear strength measured in (3) is divided by the thickness (unit: mm) of the film sample to calculate the Elmendorf tear strength. <2> Charpy impact strength is 5kJ / m 2 That's all. <1> 2. The injection molded article according to claim 1 . <3> The polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin. <1> or <2> 2. The injection molded article according to claim 1 . <4> The crosslinked resin particles (B) have a volume average particle size of 0.10 μm to 10.00 μm. <1> ~ <3> 13. The injection molded article according to any one of the above. <5> The crosslinked resin particles (B) are crosslinked using a peroxide. <1> ~ <4> 13. The injection molded article according to any one of the above items. <6> The crosslinked resin particles (B) are further crosslinked in the presence of a polyfunctional compound. <1> ~ <5> 13. The injection molded article according to any one of the above items. <7> The crosslinked resin particles (B) are not foamed. <1> ~ <6> 13. The injection molded article according to any one of the above items. <8> The proportion of the polyhydroxyalkanoate resin in the crosslinked resin particles (B) is 80% by weight or more. <1> ~ <7> 13. The injection molded article according to any one of the above items. <9> The thermoplastic resin (A) contains a biodegradable resin. <1> ~ <8> 13. The injection molded article according to any one of the above items. <10> The biodegradable resin is a polyester resin. <9> 2. The injection molded article according to claim 1 . <11> The thermoplastic resin composition further comprises a crystal nucleating agent and / or a lubricant. <1> ~ <10> 13. The injection molded article according to any one of the above items. <12> <1> ~ <11> A method for producing the injection molded article according to any one of the above, an injection step of injecting the thermoplastic resin composition into a mold; a cooling step of cooling and solidifying the thermoplastic resin composition in the mold injected in the injection step to form an injection molded article; and The method for producing an injection molded article includes a removal step of removing the injection molded article obtained in the cooling step from the inside of the mold. <13> The method further includes a step of reducing the water content of the thermoplastic resin composition prior to the injection step. <12> A method for producing the injection molded article according to claim 1. <14> In the injection step, the temperature of the thermoplastic resin composition injected into the mold is 150° C. to 250° C. <12> or <13> A method for producing the injection molded article according to claim 1. <15> In the injection step, the temperature of the mold before the thermoplastic resin composition is injected therein is 10° C. to 130° C. <11> ~ <14> 13. A method for producing an injection-molded article according to any one of the above items. EXAMPLES

[0153] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0154] [Measurement and evaluation method] <Volume average particle size> The volume average particle diameter of the crosslinked resin particles produced in Production Example 1 was measured in the state of a resin particle slurry. The measurement device used was a MicrotracMT3300EXII manufactured by Nikkiso Co., Ltd. Specifically, the particle diameter and volume of each crosslinked resin particle in the aqueous dispersion of the crosslinked resin particles were measured using the above device, and the volume average particle diameter was calculated from the results obtained by the measurement based on the above-mentioned formula (1), i.e., formula (2).

[0155] <Gel fraction> The gel fraction of the crosslinked resin particles produced in Production Example 1 was measured in a dry state. Specifically, the dried crosslinked resin particles were added to chloroform to a concentration of 0.7% by weight, and the mixture was kept at 60°C for 30 minutes to obtain a chloroform solution. The chloroform solution was then left to stand at room temperature for 3 hours, and the chloroform solution after standing for 3 hours was filtered using a membrane filter with a pore size of 0.45 μm. The weight of the filter alone was measured before the filtration. When the filtration was performed, the inside of the container and the filter were thoroughly washed with chloroform several times while filtering, thereby preventing loss. After the filtration, the gel remaining on the filter was dried, and the weight was measured together with the filter to calculate the gel fraction according to the following formula. Formula: Gel fraction = (weight of filter including dry gel - weight of filter only) / weight of crosslinked resin particles used in measurement x 100 (%) <Elmendorf tear strength> The thermoplastic resin compositions described in Production Examples 2 to 5 were used to measure the Elmendorf tear strength of the thermoplastic resin compositions by the following method.

[0156] The thermoplastic resin composition was dried under conditions of drying temperature: 80°C, drying time: 4 hours, and the moisture content was sufficiently reduced. After the moisture content was sufficiently reduced, the thermoplastic resin composition was molded into a sheet shape of 110 μm thickness at 165°C to obtain a press sheet. The press sheet was aged for 7 days under conditions of 23°C and 50% RH. Thereafter, the tear strength of the press sheet after aging for 7 days was measured using a light load tear tester (manufactured by Kumagai Riki Kogyo Co., Ltd.: NO. 2037 special specification machine) having functions and structures conforming to the standard Elmendorf tear tester specified in JIS K7128-2. The measured value was divided by the thickness (mm) of the film sample to obtain the Elmendorf tear strength (N / mm) of the thermoplastic resin composition.

[0157] <Bleed out> The surface of the press sheet after aging for 7 days before carrying out the tear strength measurement in the Elmendorf tear strength measurement was observed to confirm whether or not the plasticizer (glycerin fatty acid ester) had migrated to the surface of the press sheet. If the plasticizer appeared to have migrated to the surface, the bleed-out was recorded as "present," and if the plasticizer did not appear to have migrated to the surface, the bleed-out was recorded as "absent."

[0158] <Charpy impact strength> The rectangular injection molded articles A1 to A4 produced in Examples 1 and 2 and Comparative Examples 1 and 2 were V-notched and subjected to a Charpy impact test in accordance with JIS K 7111. The Charpy impact strength of the injection molded articles was measured in kJ / m. 2 Measurements were carried out.

[0159] <Mold releasability> In the case of producing the cup-shaped injection molded bodies B1 to B4 in Examples 1 and 2 and Comparative Examples 1 and 2, when the injection molded bodies were removed from the mold, it was confirmed whether the injection molded bodies were partly deformed and / or had cracks and wrinkles. The fact that the injection molded body removed from the mold is an injection molded body that is deformed and / or has cracks and wrinkles suggests that the injection molded body was pulled, for example, forcibly, for example, by applying force, when the injection molded body was removed from the mold. Therefore, when the injection molded body removed from the mold is an injection molded body that is deformed and / or has cracks and wrinkles, the mold releasability was evaluated as "poor". On the other hand, the fact that the injection molded article removed from the mold is an injection molded article that has not lost its shape and is free of cracks, wrinkles, etc. suggests that the injection molded article could be removed from the mold without applying excessive force, i.e., without applying excessive load to the injection molded article. Therefore, when the injection molded article removed from the mold is an injection molded article that has not lost its shape and is free of cracks, wrinkles, etc., the mold releasability was evaluated as "good."

[0160] [Compounds used] The compounds used in the following Production Examples, Examples and Comparative Examples are shown below. In the following, the terms "thermoplastic resin (A)", "thermoplastic resin (B)", "plasticizer", "crystal nucleating agent", "lubricant A", "lubricant B", "uncrosslinked resin particles", "peroxide" and "polyfunctional compound" refer to the compounds shown below unless otherwise specified. Thermoplastic resin (A): poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (Kaneka Biodegradable Polymer PHBH (registered trademark) manufactured by Kaneka Corporation), a copolymer having a monomer ratio of (3-hydroxybutyrate) / (3-hydroxyhexanoate)=94.4 / 5.6 (mol / mol), weight average molecular weight Mw: 530,000 Thermoplastic resin (B): poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (Kaneka Biodegradable Polymer PHBH (registered trademark) manufactured by Kaneka Corporation), a copolymer having a monomer ratio of (3-hydroxybutyrate) / (3-hydroxyhexanoate)=84.3 / 15.7 (mol / mol), weight average molecular weight Mw: 500,000 Plasticizer: Glycerol fatty acid ester (Biosizer, manufactured by Riken Vitamin Co., Ltd.) Nucleating agent: Pentaerythritol (Neuriser P, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) Lubricant A: Behenamide (BNT22H manufactured by Nippon Fine Chemicals) Lubricant B: Erucamide (Neutron S, manufactured by Nippon Fine Chemicals Co., Ltd.) · Uncrosslinked resin particles: poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), a copolymer having a monomer ratio of (3-hydroxybutyrate) / (3-hydroxyhexanoate)=72 / 28 (mol / mol) (hereinafter also referred to as "PHA-1"), weight average molecular weight Mw: 500,000 to 1,500,000 Peroxide: di-sec-butyl peroxydicarbonate ("Luperox (registered trademark) 225" manufactured by Arkema Yoshitomi Co., Ltd., 1-hour half-life temperature: 69°C) Polyfunctional compound: Triallyl isocyanurate [Production Example 1: Preparation of crosslinked resin particles]

[0161] In a glass vessel equipped with a stirrer, baffle, nitrogen inlet / outlet, and thermometer, the aqueous dispersion (100 parts by weight in terms of solid content) in which PHA-1 is dispersed in water, the aqueous dispersion A, 200 parts by weight of deionized water, 2 parts by weight of peroxide, 1 part by weight of sodium dioctyl sulfosuccinate, and 0.5 parts by weight of a polyfunctional compound were added to obtain a mixed dispersion. The mixed dispersion was then stirred at room temperature, and the atmosphere in the glass vessel was replaced with nitrogen at the same time as the stirring was started.

[0162] Thereafter, the mixed dispersion liquid after the nitrogen substitution was further stirred at room temperature for 1 hour to impregnate the uncrosslinked resin particles, i.e., PHA-1, with the peroxide and the polyfunctional compound in the mixed dispersion liquid, and then the temperature of the mixed dispersion liquid was raised to 75° C. After the temperature of the mixed dispersion liquid reached 75° C., the crosslinking reaction of the PHA-1 due to the decomposition of the peroxide was allowed to proceed for 3.5 hours to obtain an aqueous dispersion liquid B in which crosslinked resin particles were dispersed in water.

[0163] The pH of the obtained aqueous dispersion B was adjusted to 3.5 to 4.0 by adding an acid or alkali. The aqueous dispersion B after the pH adjustment was heated in an oven at 55°C for 15 hours and dried to prepare solidified crosslinked resin particles. The volume average particle size and gel fraction of the crosslinked resin particles were measured by the above-mentioned method. As a result, the crosslinked resin particles had a volume average particle size of 1.7 μm and a gel fraction of 95%.

[0164] [Production Example 2: Preparation of Thermoplastic Resin Composition] 70 parts by weight of thermoplastic resin (A), 30 parts by weight of the crosslinked resin particles prepared in Production Example 1, 1 part by weight of crystal nucleating agent, 0.5 parts by weight of lubricant A, and 0.5 parts by weight of lubricant B were mixed to obtain a mixture 1. The obtained mixture 1 was kneaded in a twin-screw extruder (KZW15TWIN-45WG manufactured by Technobel Co., Ltd.) with the barrel temperature heated to 140°C to 165°C at a screw rotation speed of 80 rpm to obtain a kneaded product 1. The obtained kneaded product 1 is referred to as a thermoplastic resin composition 1.

[0165] [Production Example 3: Preparation of thermoplastic resin composition] A kneaded material 2 was obtained in the same manner as in Production Example 2, except that the amount of the thermoplastic resin (A) used was changed to 50 parts by weight, and the amount of the crosslinked resin particles used was changed to 50 parts by weight. The kneaded material 2 obtained is referred to as thermoplastic resin composition 2.

[0166] [Production Example 4: Preparation of thermoplastic resin composition] A kneaded material 3 was obtained in the same manner as in Production Example 2, except that the amount of thermoplastic resin (A) used was changed to 100 parts by weight and the crosslinked resin particles were not used. The kneaded material 3 obtained is referred to as thermoplastic resin composition 3.

[0167] [Production Example 5: Preparation of thermoplastic resin composition] 10 parts by weight of thermoplastic resin (A), 90 parts by weight of thermoplastic resin (B), 4.5 parts by weight of plasticizer, 1 part by weight of crystal nucleating agent, 0.5 parts by weight of lubricant A, and 0.5 parts by weight of lubricant B were mixed to obtain mixture 2. The obtained mixture 2 was kneaded in the same manner as in Production Example 2 to obtain kneaded product 4. The obtained kneaded product 4 is referred to as thermoplastic resin composition 4.

[0168] [Example 1: Production of injection molded body] The thermoplastic resin composition 1 obtained in Production Example 2 was dried under the conditions of a drying temperature of 80° C. and a drying time of 4 hours to sufficiently reduce the moisture content. Hereinafter, the thermoplastic resin composition having the sufficiently reduced moisture content is also referred to as a "dried composition."

[0169] A part of the obtained dry composition was molded in a 15MT injection molding machine (Si-15III manufactured by Toyo Machinery & Metal Co., Ltd.) under the conditions of a cylinder temperature of 120 to 155 ° C. and a mold temperature of 40 ° C. The shape of the cavity of the mold when closed was a rectangular parallelepiped with a length of 80 mm, a width of 4 mm, and a thickness of 10 mm. As a result of the molding, a rectangular parallelepiped test piece having the same shape as the cavity, that is, a length of 80 mm, a width of 4 mm, and a thickness of 10 mm, was obtained inside the mold. The rectangular parallelepiped test piece was removed from the mold and then cured for 7 days under conditions of 23 ° C. and 50% RH, and as a result, a rectangular parallelepiped injection molded body A1 was produced. In addition, in the production of the injection molded body A1, the amount of the dry composition used was adjusted to an amount that can fill the cavity of the mold used.

[0170] Another part of the obtained dry composition was molded in a 30MT injection molding machine (Si-30V manufactured by Toyo Machinery & Metal Co., Ltd.) under the conditions of a cylinder temperature of 120 to 165°C and a mold temperature of 40°C. The shape of the cavity in the closed state of the mold was cup-shaped. As a result of the molding, a test piece having the same shape as the cavity, that is, a cup shape, was obtained inside the mold. The cup-shaped test piece was removed from the mold, and as a result, a cup-shaped injection molded body B1 was produced. In addition, in the production of the injection molded body B1, the amount of the dry composition used was adjusted to an amount that can fill the cavity of the mold used.

[0171] [Example 2: Production of injection molded body] A rectangular injection-molded body A2 and a cup-shaped injection-molded body B2 were produced in the same manner as in Example 1, except that the thermoplastic resin composition 2 prepared in Production Example 3 was used instead of the thermoplastic resin composition 1.

[0172] [Comparative Example 1: Production of injection molded article] A rectangular injection-molded body A3 and a cup-shaped injection-molded body B3 were produced in the same manner as in Example 1, except that the thermoplastic resin composition 3 prepared in Production Example 4 was used instead of the thermoplastic resin composition 1.

[0173] [Comparative Example 2: Production of injection molded article] A rectangular injection-molded body A4 and a cup-shaped injection-molded body B4 were produced in the same manner as in Example 1, except that the thermoplastic resin composition 4 prepared in Production Example 5 was used instead of the thermoplastic resin composition 1.

[0174] 〔result〕 The physical properties of the thermoplastic resin compositions 1 to 4 prepared in Production Examples 2 to 5, and the rectangular parallelepiped injection-molded bodies A1 to A4 and the cup-shaped injection-molded bodies B1 to B4 produced in Examples 1 and 2 and Comparative Examples 1 and 2 were measured and evaluated by the above-mentioned measurement and evaluation methods. The results are shown in Table 1 below. [Table 1] As shown in Production Examples 1 to 3, Examples 1 and 2, and Table 1, the thermoplastic resin compositions 1 and 2 used in the production of injection molded bodies A1, A2, B1, and B2 in Examples 1 and 2 and constituting these injection molded bodies contain 40 to 99 parts by weight of thermoplastic resin (A) and 1 to 60 parts by weight of crosslinked resin particles (B) [where the total amount of (A) and (B) is 100 parts by weight], and the crosslinked resin particles (B) contain a polyhydroxyalkanoate resin and satisfy the requirements that the gel fraction is 50% or more and the Elmendorf tear strength is 5 N / mm or more. Therefore, the injection molded bodies A1, A2, B1, and B2 correspond to the present injection molded body. In addition, the production method of the injection molded body in Examples 1 and 2 corresponds to the present production method.

[0175] On the other hand, in Comparative Example 1, the thermoplastic resin composition used to manufacture the injection molded bodies A3 and B3 does not contain crosslinked resin particles (B) and has an Elmendorf tear strength of 4 N / mm, less than 5 N / mm. In Comparative Example 2, the thermoplastic resin composition used to manufacture the injection molded bodies A4 and B4 does not contain crosslinked resin particles (B). Therefore, the injection molded bodies A3, A4, B3 and B4 do not correspond to the present injection molded body. In addition, the manufacturing methods of the injection molded bodies in Comparative Examples 1 and 2 do not correspond to the present manufacturing method.

[0176] As shown in Table 1, the injection molded articles A1 and A2 have high Charpy impact strength. Therefore, it was found that the injection molded articles A1 and A2 have excellent impact resistance.

[0177] In addition, when the thermoplastic resin compositions 1 and 2 constituting the injection molded bodies A1, A2, B1 and B2 are molded into a press sheet, no bleeding occurs in the press sheet. Therefore, like the press sheet, no bleeding occurs in the injection molded bodies A1, A2, B1 and B2, which are molded bodies of the thermoplastic resin compositions 1 and 2. Therefore, it was found that the injection molded bodies A1, A2, B1 and B2 have excellent bleeding resistance.

[0178] Furthermore, the injection molded bodies B1 and B2 did not lose their shape even after being removed from the mold, and were free of cracks, wrinkles, etc. Therefore, it was found that the injection molded bodies B1 and B2 had excellent mold releasability.

[0179] From the above, it was found that the present injection molded article has excellent impact resistance, as well as excellent mold releasability and bleed-out resistance. It was also found that the present manufacturing method can manufacture an injection molded article that has excellent impact resistance, as well as excellent mold releasability and bleed-out resistance.

[0180] In Comparative Example 1, the crosslinked resin particles (B) were not used, and as a result, the Charpy impact strength of the obtained injection molded article A3 was low. From this, it can be understood that the injection molded article of the present invention has excellent impact resistance by being molded from a thermoplastic resin composition containing 1 to 60 parts by weight of crosslinked resin particles (B) per 40 to 99 parts by weight of thermoplastic resin (A). In addition, it was found that the present manufacturing method can manufacture an injection molded article having excellent impact resistance by using a thermoplastic resin composition containing 1 to 60 parts by weight of crosslinked resin particles (B) per 40 to 99 parts by weight of thermoplastic resin (A) as a raw material.

[0181] In Comparative Example 2, the Charpy impact strength of the obtained injection molded body A4 is improved by adding a plasticizer. However, in Comparative Example 2, the mold releasability and bleed-out resistance are deteriorated due to the inclusion of the plasticizer. Here, the injection molded bodies A4 and B4 described in Comparative Example 2 correspond to conventional injection molded bodies containing a plasticizer and having excellent impact resistance. From this, in the present injection molded body, by molding a thermoplastic resin composition containing the above-mentioned amount of crosslinked resin particles (B) without using a plasticizer, the impact resistance is improved, while the deterioration of the mold releasability and bleed-out resistance caused by the plasticizer can be prevented. Therefore, it was found that the present injection molded body is more excellent in mold releasability and bleed-out resistance than the conventional injection molded body containing a plasticizer and having excellent impact resistance. In addition, it was found that the present manufacturing method can manufacture an injection molded body having excellent mold releasability and bleed-out resistance in addition to excellent impact resistance, compared to the conventional manufacturing method of an injection molded body having excellent impact resistance using a plasticizer. [Industrial Applicability]

[0182] The injection molded article has excellent impact resistance, as well as excellent mold releasability and bleed-out resistance. Therefore, the injection molded article and the manufacturing method can be used to manufacture products that require impact resistance, productivity, and appearance quality. Examples of such products include containers, home appliance parts, and vehicle parts.

Claims

1. An injection molded article obtained by molding a thermoplastic resin composition, The thermoplastic resin composition comprises 40 to 99 parts by weight of a thermoplastic resin (A) and 1 to 60 parts by weight of crosslinked resin particles (B) (wherein the total amount of (A) and (B) is 100 parts by weight); The crosslinked resin particles (B) contain a polyhydroxyalkanoate resin and have a gel fraction of 50% or more, The thermoplastic resin composition has an Elmendorf tear strength of 5 N / mm or more as measured by the following methods (1) to (4): (1) The thermoplastic resin composition is molded into a sheet having a thickness of 110 μm to obtain a press sheet. (2) The press sheet obtained in step (1) is aged under conditions of 23° C. and 50% RH for 7 days to obtain a film sample. (3) The film sample obtained in step (2) is subjected to measurement of tear strength (unit: N) according to the Elmendorf tear method specified in JIS K7128-2. (4) The tear strength measured in (3) is divided by the thickness (unit: mm) of the film sample to calculate the Elmendorf tear strength.

2. Charpy impact strength is 5 kJ / m 2 The injection molded article according to claim 1 .

3. 2. The injection molded article according to claim 1, wherein the polyhydroxyalkanoate resin is a poly(3-hydroxyalkanoate) resin.

4. 2. The injection molded article according to claim 1, wherein the crosslinked resin particles (B) have a volume average particle size of 0.10 μm to 10.00 μm.

5. 2. The injection molded article according to claim 1, wherein the crosslinked resin particles (B) are crosslinked using a peroxide.

6. 2. The injection molded article according to claim 1, wherein the crosslinked resin particles (B) are further crosslinked in the presence of a polyfunctional compound.

7. 2. The injection molded article according to claim 1, wherein the crosslinked resin particles (B) are not expanded.

8. 2. The injection molded article according to claim 1, wherein the crosslinked resin particles (B) contain the polyhydroxyalkanoate resin in an amount of 80% by weight or more.

9. The injection molded article according to claim 1 , wherein the thermoplastic resin (A) comprises a biodegradable resin.

10. The injection molded article according to claim 9 , wherein the biodegradable resin is a polyester-based resin.

11. The injection molded article according to claim 1 , wherein the thermoplastic resin composition further comprises a crystal nucleating agent and / or a lubricant.

12. A method for producing the injection molded article according to any one of claims 1 to 11, an injection step of injecting the thermoplastic resin composition into a mold; a cooling step of cooling and solidifying the thermoplastic resin composition in the mold injected in the injection step to form an injection molded article; and The method for producing an injection molded article includes a removal step of removing the injection molded article obtained in the cooling step from the inside of the mold.

13. The method for producing an injection molded article according to claim 12, further comprising a step of reducing a moisture content of the thermoplastic resin composition prior to the injecting step.

14. The method for producing an injection molded article according to claim 12, wherein the temperature of the thermoplastic resin composition injected into the mold in the injection step is 150°C to 250°C.

15. The method for producing an injection molded article according to claim 12, wherein in the injection step, the temperature of the mold before the thermoplastic resin composition is injected therein is 10°C to 130°C.

Citation Information

Patent Citations

  • Biodegradable polyester resin composition and method for producing the same

    JP2004161802A